Polymer-cyclic molecular structure and method for producing same
Patent Information
- Application Number
- JP2021023787
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-02-20
- Filing Date
- 2021-02-17
- Publication Date
- 2025-02-17
- Estimated Expiration
- 2041-02-17
AI Technical Summary
【0009】 本発明によれば、鎖状ポリマーの軸方向(鎖状ポリマーを包接する環状分子の軸方向)により厚みのある構造体が提供される。また、そのような構造体の製造方法は、エネルギー、コスト又は製造時間が低減されている点で有利である。
Smart Images

Figure 0007630158000003 
Figure 0007630158000004 
Figure 0007630158000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a structure having a plurality of pseudopolyrotaxanes and / or polyrotaxanes each having a chain polymer that pierces the opening of a cyclic molecule in an inclusive manner, and a method for producing the same. [Background technology]
[0002] In recent years, nanosheets with a thickness of 100 nm or less have been increasingly applied to medicines, catalysts, optical materials, electrodes, biomaterials, etc. Patent Document 1 discloses an isolated nanosheet having a plurality of pseudopolyrotaxanes and / or polyrotaxanes in which the openings of cyclic molecules such as cyclodextrin are pierced and enclosed by linear molecules, and the linear molecules have first linear molecules, some of which have an ionizable group that ionizes in water or an aqueous solution. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] WO2020 / 013215 Summary of the Invention [Problem to be solved by the invention]
[0004] As described in Patent Document 1, a single-layer nanosheet in which one pseudopolyrotaxane and / or polyrotaxane molecule is arranged in the thickness direction is thin, and therefore it is not possible to contain a large amount of a substance such as a drug in the sheet. To Chain Polymer but It would be advantageous if a structure could be designed in which pseudopolyrotaxanes and / or polyrotaxanes formed by inclusion in a skewered shape extend not only in parallel but also in series.
[0005] The thickness of the sheet can be increased by increasing the length of the chain polymer, but a single chain polymer of Many cyclic molecules but The pseudopolyrotaxane and / or polyrotaxane must be inclusively formed, and the production of such pseudopolyrotaxane and / or polyrotaxane requires a large amount of reaction energy, is costly, and is time-consuming.
[0006] An object of the present invention is to provide a structure having a plurality of pseudopolyrotaxanes and / or polyrotaxanes that are thicker than conventional nanosheets, and a method for producing the same. [Means for solving the problem]
[0007] As a result of intensive investigations to solve the above problems, the present inventors designed a chain polymer structure such that both ends of the chain polymer constituting the pseudopolyrotaxane and / or polyrotaxane are accommodated without protruding from a pillar structure, i.e., a column, composed of a plurality of cyclic molecules, and discovered that a plurality of pseudopolyrotaxanes and / or polyrotaxanes can be stacked in series due to non-covalent interactions between adjacent cyclic molecules of adjacent pseudopolyrotaxanes and / or polyrotaxanes, thereby completing the present invention.
[0008] The present invention encompasses the embodiments described below. Item 1. Opening of cyclic molecules To Incorporated into a skewer shape Be A structure having a plurality of pseudopolyrotaxanes and / or polyrotaxanes each having a chain polymer, A structure in which at least a portion of a plurality of pseudopolyrotaxanes and / or polyrotaxanes are arranged in series with one another. Item 2. The structure according to Item 1, wherein the chain polymer is a single chain. Item 3. The chain polymer has three or more openings of cyclic molecules per chain polymer. To Incorporated into a skewer shape Be 3. The structure according to item 1 or 2. Item 4. The structure according to any one of Items 1 to 3, wherein at least a portion of the plurality of pseudopolyrotaxanes and / or polyrotaxanes are arranged in parallel with each other. Item 5. The structure according to any one of Items 1 to 4, further comprising a substance bound to a chain polymer, bound to a cyclic molecule, or retained inside a space between a plurality of pseudopolyrotaxanes and / or polyrotaxanes, an opening formed by one cyclic molecule, or a space formed by a plurality of cyclic molecules. Item 6. The structure according to item 5, wherein the substance is at least one selected from the group consisting of a drug, a fluorescent substance, and a chromogenic enzyme. Item 7. The structure according to any one of Items 1 to 6, wherein the length of the chain polymer is 1 nm to 2000 nm. Item 8. The structure according to any one of Items 1 to 7, wherein the chain polymer comprises a portion made of polyethylene glycol (PEG) or polypropylene glycol (PPG). Item 9. The structure according to any one of Items 1 to 8, wherein the cyclic molecule is at least one selected from the group consisting of cyclodextrin, crown ether, pillararene, calixarene, cyclophane, and derivatives thereof. Item 10. The structure according to any one of Items 1 to 9, wherein the one or more through holes penetrate the structure and occupy a space larger than the volume occupied by one pseudopolyrotaxane and / or polyrotaxane. Item 11. The structure according to any one of Items 1 to 10, wherein the structure is any one of the following (a) to (c): (a) A rod-shaped structure in which the weight-average molecular weight of the chain polymer is 200 to 10,000. (b) A cube-shaped structure in which the weight-average molecular weight of the chain polymer is 1,000 to 20,000. (c) A sheet-like structure in which the weight-average molecular weight of the chain polymer 10 is 2,000 to 200,000. Item 12. Opening of cyclic molecules To Incorporated into a skewer shape Be A method for producing a structure having a plurality of pseudo-polyrotaxanes and / or polyrotaxanes each having a chain polymer, comprising: A method comprising a step of allowing a plurality of pseudo-polyrotaxanes and / or polyrotaxanes contained in a column in which both ends of a chain polymer are made of a plurality of cyclic molecules to interact with each other, thereby arranging at least a portion of the plurality of pseudo-polyrotaxanes and / or polyrotaxanes in series with each other. Effect of the Invention
[0009] According to the present invention, the axial direction of the chain polymer ( of Inclusion do The axial direction of the cyclic molecules provides a thick structure. Furthermore, the method for producing such a structure is advantageous in that it reduces energy, cost, or production time. [Brief description of the drawings]
[0010] [Figure 1] (A) Schematic diagram showing a cyclic molecule and a linear polymer. (B) Schematic diagram showing a pseudopolyrotaxane and / or a polyrotaxane unit. [Diagram 2] FIG. 2 is a schematic perspective view of a structure according to one embodiment of the present invention formed by aggregation of a plurality of pseudopolyrotaxanes. [Diagram 3] Schematic diagram showing the relationship between the molecular weight of linear polymers and the shape of structures. (A) An example of rod-shaped structures produced when PEO is a short chain, (B) an example of cube-shaped structures produced when PEO is longer than (A), (C) an example of sheet-shaped structures produced when PEO is even longer than (B), and (D) an example of single-layer nanosheet-shaped structures produced when PEO is even longer than (C). [Figure 4] (A) Branched PEO, (B) schematic diagram of a sheet of a structure using the branched PEO of (A), (C) schematic diagram showing the connected state of the sheet of (B). [Diagram 5](A)-(F) Diagrams showing the relationship between the order of chemical bonds of γ-CD to segments of different compositions in the linear polymer and the shape of the structure. (A) Tripolymer with three segments, the central part being PPO and both ends being PEO at 0.2K, (B) Tripolymer with three segments, the central part being PPO and both ends being PEO at 1.1K, (C) Tripolymer with three segments, the central part being PPO and both ends being PEO at 6.5K, (D) Schematic diagram of the structure formed using the linear polymer in Figure 5(A) (left) and an enlarged view of the circled part (right), (E) Schematic diagram of the structure formed using the linear polymer in Figure 5(B) (left) and an enlarged view of the circled part (right), (F) Schematic diagram of the structure formed using the linear polymer in Figure 5(C) (left) and an enlarged view of the circled part (right). [Figure 6] (A) A schematic front view of a pseudo-polyrotaxane in which the linear polymer is polypropylene oxide (PPO), (B) a schematic front view of a pseudo-polyrotaxane in which the linear polymer is polyethylene oxide (PEO), (C) a schematic front view of a pseudo-polyrotaxane in which the linear polymer extends from one end of a column consisting of a series of cyclic molecules to the other end, (D) a schematic front view of a pseudo-polyrotaxane in which the linear polymer extends beyond the bottom end of a column consisting of six cyclic molecules but not to the top end, (E) a schematic front view of a pseudo-polyrotaxane in which the linear polymer does not reach the top or bottom end of a column consisting of six cyclic molecules, and (F) a schematic front view showing a series of cyclic molecules without a linear polymer. [Figure 7] FIG. 2 is a schematic perspective view of a particular embodiment of a structure with a through hole. [Figure 8] (A) Photograph of the formation of PPR_EO400 observed with the naked eye, (B) photograph of optical microscope observation, (C) photograph of SEM observation. [Figure 9] (A) SEM image of the structure of PPR_EO400 (PEO with a molecular weight of 400), (B) SEM image of the structure of PPR_EO4k (PEO with a molecular weight of 4000), (C) SEM image of the structure of PPR_EO6k (PEO with a molecular weight of 6000), (D) SEM image of the structure of PPR_EO20k (PEO with a molecular weight of 20000). [Figure 10]WAXS profiles of PPR_EO400, PPR_EO2k, PPR_EO4k, PPR_EO6k, and PPR_EO20k, respectively. [Figure 11] (A) SEM image of the structure of PPR_PO400 (PPO with a weight molecular weight of 400), (B) SEM image of the structure of PPR_PO2k (PPO with a weight molecular weight of 2000), (C) SEM image of the structure of PPR_PO4k (PPO with a weight molecular weight of 4000), [Figure 12] (A) SEM image of PPR_EO4PO56EO4, (B) SEM image of PPR_EO25PO56EO25, (C) SEM image of PPR_EO147PO56EO147, (D) WAXS profile of PPR_EO147PO56, (E) AFM image and height profile of PPR_EO147PO56 [Figure 13] Micrograph of a nanosheet with through-holes. [Figure 14] 1 is a micrograph of the microstructure of Example 6. [Figure 15] 13 is a micrograph of the microstructure of Example 7. [Figure 16] 4(A) to (D) are micrographs of the microstructure of Example 8. [Figure 17] 13 is a micrograph of the structure of Example 9. [Figure 18] 13 is a micrograph of the microstructure of Example 10. [Figure 19] Micrographs of the microstructure of Example 11. (A) Low magnification, (B) high magnification. Scale bars indicate lengths. [Figure 20] Micrographs of the structure of Example 12. (A) Low magnification, (B) Medium magnification (enlarged area surrounded by dotted line in FIG. 20A), (C) High magnification (enlarged area surrounded by dotted line in FIG. 20B). Scale bars indicate lengths. [Figure 21] FIG. 1 is a micrograph of the structure of Example 13. The inset in the upper right corner is a magnified photograph. [Figure 22] Micrographs of the microstructure of Example 14. (A) Phase contrast microscope, (B) Fluorescence microscope. Scale bars indicate lengths. [Diagram 23]Micrographs of the Skin_β-CD / EO75PO30EO75 structure of Example 15. (A) Before deposition, (B) after deposition. [Figure 24] Micrographs of the hair_β-CD / EO75PO30EO75 structure of Example 15. (A) Before attachment, (B) after attachment. [Diagram 25] Micrographs of the lens_β-CD / EO75PO30EO75 structure of Example 15. (A) Before deposition, (B) after deposition. [Figure 26] Micrograph of the eye_PPR_EO147PO56EO147 structure of Example 15. [Figure 27] Figure 16 shows the absorbance of the β-CD / EO75PO30EO75 structure of Example 16 versus wavelength of incident light. [Figure 28] SEM images of (A) the porous membrane, (B) pоre-β-CD / EO75PO30EO75 (5 mL), and (C) pоre-β-CD / EO75PO30EO75 (20 mL). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Hereinafter, an embodiment of the present invention will be described with reference to the drawings.
[0012] In this specification, a polymer refers to a compound consisting of molecules having a repeating structure derived from a monomer, which is a monomer. The chain polymer is preferably a single-chain polymer, but may be a polymer having branches from the main chain if the cyclic molecules can move or rotate on the chain polymer.
[0013] In this specification, the thickness direction of the structure refers to the longitudinal direction of the pseudopolyrotaxane and / or polyrotaxane unit, in other words, the direction along the longitudinal direction of the chain polymer constituting the pseudopolyrotaxane and / or polyrotaxane and / or the direction along the axial direction of the cyclic molecule.
[0014] In this specification, the formation of the structure can be confirmed by small angle X-ray scattering measurement, phase contrast optical microscope observation, atomic force microscope observation, or scanning electron microscope observation.
[0015] In this specification, the term "polyrotaxane" refers to a cyclic molecule and an opening of the cyclic molecule. To Incorporated into a skewer shape Be The term "pseudopolyrotaxane" refers to a molecular assembly consisting of a cyclic molecule and a linear polymer that encapsulates the opening of the cyclic molecule in a skewered manner, and that has the above-mentioned blocking group at only one end of the linear polymer or has no blocking group at either end of the linear polymer.
[0016] As used herein, the term "cyclodextrin" refers to a cyclic oligosaccharide in which D-glucose is linked via α-1,4 glycosidic bonds to form a ring structure.
[0017] In this specification, polyethylene oxide (PEO) having a weight average molecular weight of 20,000 or less may be referred to interchangeably as polyethylene glycol (PEG).
[0018] In this specification, polypropylene oxide (PPO) having a weight average molecular weight of 20,000 or less may be referred to interchangeably as polypropylene glycol (PPG).
[0019] FIG. 1(A) shows a cyclic molecule 20 and a chain polymer 10. The cyclic molecule 20 has a hollow, approximately truncated cone-shaped body 22 and an opening 24 defined by the body 22. The chain polymer 10 has a polymer body 12, and in this example, one end of the polymer body 12 is provided with a modifying group 18 consisting of an ionizable group or a non-ionizable group. FIG. 1(B) shows the opening 24 of the cyclic molecule 20. To Incorporated into a skewer shape Be1 shows a pseudopolyrotaxane and / or polyrotaxane 2 having a chain polymer 10 that is connected to the three cyclic molecules 20. In this figure, the chain polymer 10 extends into the interior of the openings 24 of all three cyclic molecules 20, but both ends 14, 16 of the chain polymer 10 do not reach both ends of the opening 6, and the entire chain polymer 10 is accommodated in the opening 6 that is partitioned and formed by the three linked cyclic molecules 20.
[0020] Without wishing to be bound by theory, in the pseudopolyrotaxane and / or polyrotaxane 2 shown in FIG. 1(B), the cyclic molecules 20 present in the central portion are aggregated in a columnar shape, i.e., a pillar shape, and the columnarized cyclic molecules 20 become hydrophobic on the outer surface. Therefore, a plurality of pseudopolyrotaxanes and / or polyrotaxanes 21 self-assemble with each other via the hydrophobic columnar cyclic molecules 20 to form a structure 1 as shown in one embodiment of FIG. 2. At this time, since a plurality of cyclic molecules 20 are aggregated to one chain polymer 10, the chain polymer 10 is stretched in an approximately linear shape, and there is less steric hindrance between the chain polymers 10 compared to when the cyclic molecules 20 are not present on the chain polymer 10. Therefore, the chain polymers 24 can be arranged at a higher density in the structure 1. The configuration of the structure 1 will be described in detail later.
[0021] The present inventors have previously To Incorporated into a skewer shape Be However, a single-layer nanosheet in which one pseudopolyrotaxane and / or polyrotaxane is arranged in the thickness direction of the nanosheet is thin, and there was a problem that the sheet could not contain a large amount of a substance such as a drug.
[0022] Therefore, the present inventors have designed a chain polymer structure such that both ends of the chain polymer constituting the pseudopolyrotaxane and / or polyrotaxane are accommodated in a pillar structure, i.e., a column, composed of multiple cyclic molecules, and have surprisingly found that multiple pseudopolyrotaxanes and / or polyrotaxanes can be stacked in series due to non-covalent interactions between adjacent cyclic molecules of adjacent pseudopolyrotaxanes and / or polyrotaxanes. Non-covalent interactions include, but are not limited to, ionic bonds, hydrogen bonds, van der Waals forces, etc.
[0023] Furthermore, we attempted to control the structure of structures composed of multiple pseudopolyrotaxanes and / or polyrotaxanes by designing the structure of the chain polymer under various conditions, and found that the shape of the structure could be controlled by changing the molecular weight, hydrophilicity and hydrophobicity, topology, and polymer block of the chain polymer.
[0024] For example, a structure in which the cyclic molecule 20 is γ-cyclodextrin (hereinafter, γ-CD) and the chain polymer 10 is polyethylene oxide (PEO) will be used for explanation.
[0025] First, regarding the effect of the molecular weight of the chain polymer, the dependence of the crystal growth of the structure on the length of the PEO axis is summarized in Figure 3 (A)-(C). When the chain polymer 10 is PEO, the cyclic molecule 20 forms a double-stranded complex with the chain polymer 10.
[0026] As shown in FIG. 3(A), when the molecular weight of the chain polymer 10 is small and the axis is short, a rod-like structure is formed in which the pseudopolyrotaxane and / or polyrotaxane 2 are stacked long in the c-axis direction, i.e., in the direction parallel to the main axis of the chain polymer 10. In other words, it shows that the crystal growth of the cyclic molecule 20 in the c-axis direction is faster than the crystal growth in the a-axis and b-axis directions perpendicular to the c-axis. In contrast, as the axis of the chain polymer 10 becomes longer, the side length of the structure in the c-axis direction becomes shorter. This shows that in a longer chain polymer 10, the crystal growth of the cyclic molecule 20 is faster along the a-axis and b-axis compared to the c-axis. It is considered that when the length of the pseudopolyrotaxane and / or polyrotaxane 2 is short, the lateral interaction is weaker than that of the longer pseudopolyrotaxane and / or polyrotaxane 2, and the pseudopolyrotaxane and / or polyrotaxane 2 extends in the c-axis direction.
[0027] In the example shown in Figure 3(B), when the length of the chain polymer 10 is made longer than that of Figure 3(A), the lateral interaction becomes greater than that of Figure 3(A), and a cube-shaped structure is formed in which the length in the c-axis direction is equal to the lengths in the a-axis and b-axis directions.
[0028] In the example shown in FIG. 3(C), when the length of the chain polymer 10 is made longer than that in FIG. 3(B), a sheet-like structure is formed that is longer in the a-axis and b-axis directions than in the c-axis direction.
[0029] When the length of the chain polymer 10 is made longer than that shown in Fig. 3(C), the chain polymer 10 becomes bent as shown in Fig. 3(D), and the bent portions of the chain polymer 10 hinder crystal growth along the c-axis of the cyclic molecules 20, forming a sheet-like structure. The portions of the chain polymer 10 including the bent portions protrude from the cyclic molecules 20. In this way, by changing the length or molecular weight of the chain polymer 10, the behavior of the crystal of the structure formed by the cyclic molecules 20 can be controlled.
[0030] Next, the effect of hydrophilicity and hydrophobicity of the chain polymer 10 will be described. When the cyclic molecule 20 is γ-CD and the chain polymer 10 is PEO, various shapes of structures are formed with the change in molecular weight as described above. In contrast, when the chain polymer 10 is hydrophobic polypropylene oxide (PPO) instead of hydrophilic PEO, the chain polymer 10 changes to a rod shape in which the length in the c-axis direction is larger than the length in the a- and b-axis directions, a cube shape in which the length in the c-axis direction is approximately equal to the length in the a- and b-axis directions, a sheet shape in which the length in the c-axis direction is smaller than the length in the a- and b-axis directions, and a random (disordered) shape as the chain polymer 10 becomes longer. In this way, the hydrophilicity and hydrophobicity of the chain polymer 10 can also affect the behavior of the crystal of the structure.
[0031] Without wishing to be bound by theory, the above phenomenon is believed to occur because, when the chain polymer 10 is hydrophilic, hydration occurs at the surface of the structure, stabilizing the structure, whereas, when the chain polymer 10 is hydrophobic, hydrophobic aggregation competes with the crystallization of γ-CD, resulting in disorder.
[0032] Next, the effect of the topology of the chain polymer 10 will be described. When the chain polymer 10 is a single-chain PEO, structures of various shapes are formed with the change in molecular weight as described above. In contrast, when PEO having a branch point P in FIG. 4(A) is used as the chain polymer 10', the branch point P suppresses crystal growth as shown in FIG. 4(B), and a sheet-like structure of uniform thickness is formed, but the chain polymer 10' acts as a bridge to connect the sheets together as shown in FIG. 4(C). In this way, the topology of the chain polymer 10 can affect the behavior of the crystals of the structure.
[0033] Next, the effect of changing the polymer block configuration will be described. For example, a block triblock polymer shown in Figures 5(A)-(C) is used as the chain polymer 10, in which the central block is PPO with a molecular weight of 3.3k ("k" stands for kilo, as well as the following) and the blocks on both sides are PEO with molecular weights of 0.2k, 1.1k, and 6.5k, respectively. In this case, the block structures shown in Figures 5(D)-(F) are formed, respectively. In either case, the strength of the interaction with γ-CD is stronger between γ-CD and PPO than between γ-CD and PEO, and γ-CD is localized in the center of the chain polymer 10 in the axial direction. By utilizing this, a hydrophobic PPO block is placed in the center of a chain polymer, hydrophilic PEO blocks are placed at both ends, and the length of the PEO blocks is made sufficiently long, so that the PEO blocks at both ends of the chain polymer 10 protrude from columns composed of multiple γ-CDs, and a monolayer sheet having a uniform thickness, that is, a sheet in which one pseudopolyrotaxane and / or polyrotaxane molecule is aligned in the thickness direction, can be produced.
[0034] Here, the structure of the structure according to one embodiment of the present invention will be described.
[0035] As shown in FIG. 2, the structure 1 according to one embodiment of the present invention has a plurality of pseudopolyrotaxanes and / or polyrotaxanes 2, and each pseudopolyrotaxane and / or polyrotaxane 2 has an opening of a cyclic molecule 20. To Incorporated into a skewer shape Be The structure 1 has a chain polymer 10, in which at least a portion of the pseudo-polyrotaxanes and / or polyrotaxanes 2 are arranged in series with each other. Another portion of the pseudo-polyrotaxanes and / or polyrotaxanes 2 are arranged in parallel with each other. A plurality of pseudo-polyrotaxanes and / or polyrotaxanes 2 are arranged in the thickness direction of the sheet of the structure 1 and in each of two directions perpendicular to the thickness direction of the sheet. Specifically, in this figure, two pseudo-polyrotaxanes and / or polyrotaxanes are arranged in series, and 17×10 pairs of pseudo-polyrotaxanes and / or polyrotaxanes 2 are arranged in parallel.
[0036] "Having a plurality of pseudopolyrotaxanes and / or polyrotaxanes" refers to having a plurality of pseudopolyrotaxanes, having a plurality of polyrotaxanes, or having at least one pseudopolyrotaxane and / or polyrotaxane.
[0037] The phrase "multiple pseudo-polyrotaxanes and / or polyrotaxanes are arranged in series" refers to multiple pseudo-polyrotaxanes and / or polyrotaxanes stacked and arranged in the axial direction of their cyclic molecules. It is preferable that the axial directions of one pseudo-polyrotaxane and / or polyrotaxane arranged in series with another pseudo-polyrotaxane and / or polyrotaxane are approximately the same, and that the cyclic molecules are arranged in a row, but as long as the cyclic molecules are stacked and arranged in the axial direction of the cyclic molecules, the positions of the individual cyclic molecules may be slightly shifted in the direction perpendicular to the axial direction.
[0038] The phrase "multiple pseudo-polyrotaxanes and / or polyrotaxanes are arranged in parallel" means that multiple pseudo-polyrotaxanes and / or polyrotaxanes are arranged approximately parallel to each other. It is preferable that the axial directions of the pseudo-polyrotaxanes and / or polyrotaxanes arranged in parallel to each other and the other pseudo-polyrotaxanes and / or polyrotaxanes are approximately parallel to each other.
[0039] The size of the structure 1 is not particularly limited, but the dimensions of the a-axis, b-axis, and c-axis directions of the crystal of the structure 1 are usually on the order of nanometers (1 nm or more, less than 1000 nm) or micrometers (1 μm or more, less than 1000 μm). The pharmacokinetic behavior in the body differs depending on the particle size of the structure 1. For example, ≧2 mm is taken up by liver cells, ≧300 to 400 nm is captured and excreted by macrophages, ≧200 nm is processed in the spleen, and ≧100 nm passes between vascular endothelial cells. Therefore, the size of the structure 1 can be selected according to the purpose and the structure 1 can be designed. In addition, the structure 1 having a dimension of 1 μm or more along at least one of the a-axis, b-axis, and c-axis may be referred to as a "microstructure" in this specification.
[0040] The structure 1 may have a rod shape in which the length in the c-axis direction is greater than the lengths in the a- and b-axis directions, a cube shape in which the length in the c-axis direction is approximately equal to the lengths in the a- and b-axis directions, or a sheet shape in which the length in the c-axis direction is smaller than the lengths in the a- and b-axis directions. When the structure 1 is in the form of a sheet, the shape of the sheet when viewed in a plane may be substantially square, substantially rectangular, rhombic, or polygonal (the number of sides is 3, 4, 5, 6, or more). Furthermore, the structure 1 may have a tent shape, i.e., a hollow pyramid shape, a polyhedron shape, a column shape (including a rectangular column shape or a cylindrical shape; solid or hollow), or a sphere shape (including a solid or hollow shape). FIG. 2 shows an example of the sheet-shaped structure 1.
[0041] When the structure 1 is rod-shaped, the thickness (length in the c-axis direction) is preferably 100 nm or more, more preferably 100 nm to 1000 μm, and even more preferably 200 nm to 100 μm, and the lengths in each of the a-axis and b-axis directions are preferably 50 nm or more, more preferably 50 nm to 100 μm, and even more preferably 100 nm to 10 μm.
[0042] When the structure 1 is cubic, the thickness (length in the c-axis direction) and the lengths in the a-axis and b-axis directions are preferably 50 nm or more, more preferably 50 nm to 1000 μm, and further preferably 100 nm to 100 μm.
[0043] When the structure 1 is in the form of a sheet, the thickness (length in the c-axis direction) is preferably 50 nm or more, more preferably 50 nm to 100 μm, and even more preferably 100 nm to 10 μm, and the lengths in each of the a-axis and b-axis directions are preferably 100 nm or more, more preferably 100 nm to 1000 μm, and even more preferably 200 nm to 100 μm.
[0044] Within the multiple cyclic molecules 20 of each pseudopolyrotaxane and / or polyrotaxane 2, one chain polymer 10 may be accommodated, or multiple (for example, two) chain polymers 10 may be accommodated.
[0045] The chain polymer 10 may be linear or branched, but in order to control the structure of the structure and prevent linkage between structures 1, it is preferable that the chain polymer 10 is a single chain. In one preferred embodiment, all of the multiple chain polymers 10 constituting each pseudopolyrotaxane and / or polyrotaxane 2 of the structure 1 are single chains. In another preferred embodiment, some of the multiple chain polymers 10 constituting each pseudopolyrotaxane and / or polyrotaxane 2 of the structure 1 are single chains, and the remaining part are branched chains.
[0046] When the pseudopolyrotaxane and / or polyrotaxane 2 has a blocking group, examples of the blocking group include, but are not limited to, a dinitrophenyl group, cyclodextrin, an adamantane group, a trityl group, fluorescein, pyrene, etc. Methods for introducing a blocking group into a chain polymer are known, and for example, the method described in Harada et al., Nature, 1992, 356, 325-327 can be referred to.
[0047] The chain polymer 10 has a repeating structure derived from a monomer, and the skeleton forming such a repeating structure may be selected from the group consisting of polyvinyl alcohol, polyvinylpyrrolidone, poly(meth)acrylic acid; cellulose; modified cellulose such as carboxymethyl cellulose, hydroxyethyl cellulose, and hydroxypropyl cellulose; polyacrylamide, polyethylene oxide, polypropylene oxide, polytetrahydrofuran, polyvinyl acetal, polyvinyl methyl ether, polyamine, polyethyleneimine, casein, gelatin, and starch; polyolefins such as polyethylene and polypropylene, copolymers of olefins such as ethylene or propylene with other olefins, and polyesters. The polyimide may be selected from the group consisting of polyamides and polyimides such as polyisoprene and polybutadiene; polysiloxanes, polysulfones, polyimines, polyacetic anhydrides, polyureas, polysulfides, polyphosphazenes, polyketones, polyphenylenes, and derivatives thereof.
[0048] In terms of interaction with the cyclic molecule 20, the repeating structure of the chain polymer 10 is preferably at least one selected from the group consisting of, for example, polyethylene glycol, polyisoprene, polyisobutylene, polybutadiene, polypropylene glycol, polytetrahydrofuran, polydimethylsiloxane, polyethylene, polypropylene, polyvinyl alcohol, and polyvinyl methyl ether, and more preferably at least one selected from the group consisting of polyethylene oxide and polypropylene oxide.
[0049] The weight average molecular weight of the chain polymer 10 is not limited, but is preferably 200 to 200,000, more preferably 200 to 50,000, and further preferably 200 to 20,000.
[0050] When the structure 1 is rod-shaped, the weight average molecular weight of the chain polymer 10 is preferably 200-10,000, more preferably 200-2,000, and further preferably 200-1,000.
[0051] When the structure 1 is cubic, the weight average molecular weight of the chain polymer 10 is preferably 1,000 to 20,000, more preferably 2,000 to 10,000, and further preferably 2,000 to 6,000.
[0052] When the structure 1 is a sheet, the weight average molecular weight of the chain polymer 10 is preferably 2,000 to 200,000, more preferably 4,000 to 100,000, and further preferably 6,000 to 50,000.
[0053] In one preferred embodiment, the chain polymer 10 is water-soluble, and examples thereof include at least one selected from the group consisting of polyethylene oxide (polyethylene glycol), polypropylene oxide (polypropylene glycol), polyvinyl alcohol, polyethyleneimine, polyacrylic acid, polymethacrylic acid, polyacrylamide, cellulose derivatives such as hydroxypropyl cellulose, and polyvinylpyrrolidone, and more preferably at least one selected from the group consisting of polyethylene glycol and polypropylene glycol.
[0054] The weight average molecular weight of the water-soluble chain polymer 10 is preferably 200 to 200,000, more preferably 200 to 50,000, and further preferably 200 to 20,000.
[0055] The chain polymer 10 may have a portion formed by polymerization of one type of monomer or may be a polymer consisting of only such a portion, may have a copolymer formed by polymerization of two types of monomer or may be a polymer consisting of only such a copolymer portion, or may have a terpolymer formed by polymerization of three types of monomer or may be a polymer consisting of only such a terpolymer portion. Examples of such portions include the above-mentioned examples of the skeleton forming the repeating structure. In particular, examples of such portions include at least one selected from the group consisting of polyethylene glycol, polyisoprene, polyisobutylene, polybutadiene, polypropylene glycol, polytetrahydrofuran, polydimethylsiloxane, polyethylene, polypropylene, polyvinyl alcohol, and polyvinyl methyl ether, but are not limited thereto.
[0056] The chain polymer 10 may be a block copolymer having two blocks. The chain polymer 10 may be a block copolymer having three blocks. When both ends of the chain polymer 10 are accommodated in a column consisting of a plurality of cyclic molecules 20, adjacent pseudopolyrotaxanes and / or adjacent cyclic molecules 20 of polyrotaxanes can be arranged in series by non-covalent interaction. In order for both ends of the chain polymer 10 to be accommodated in a column consisting of a plurality of cyclic molecules 20, it is preferable that no hydrophilic PEO block is arranged at both ends of the chain polymer 10, or that even if a hydrophilic PEO block is arranged, the length of the hydrophilic PEO block is 0.20 nm or less.
[0057] Preferred examples of the linear polymer 10 include, but are not limited to, a single block polymer made of polyethylene oxide (PEO), a diblock polymer made of a block of polyethylene oxide (PEO) and a block of polypropylene oxide (PPO), a triblock copolymer having a block of polyethylene oxide (PEO), a block of polypropylene oxide (PPO), and a block of polyethylene oxide (PEO) in that order, etc. A triblock polymer made of PEO-PPO-PEO is preferred in that PPO is more hydrophobic than PEO and cyclic molecules are more selectively aligned and included in PPO.
[0058] Each block of the block polymer preferably consists of only repeating units derived from one monomer, but may have a first spacer group between one repeating unit and the next repeating unit, and may have a second spacer group between adjacent blocks, which may be the same as or different from the first spacer group.
[0059] Examples of the first and / or second spacer group include, but are not limited to, a linear or branched alkyl group having 1 to 20 carbon atoms, a linear or branched ether group having 1 to 20 carbon atoms, a linear or branched ether having 1 to 20 carbon atoms, a linear or branched ester having 1 to 20 carbon atoms, and an aromatic group having 6 to 24 carbon atoms, such as a phenyl group.
[0060] When the opening of the cyclic molecule 20 is held in a state in which it is penetrated by the chain polymer 10, the cyclic molecule 20 is held at any part of the chain polymer 10. of Inclusion death A chain polymer 10 formed by polymerization of one type of monomer may be used. of Inclusion death or one of the two moieties of the block copolymer of Inclusion death Alternatively, one of the three moieties of the block copolymer, particularly the middle moiety of the three moieties, may be of Inclusion death This is also fine.
[0061] When the linear polymer 10 is a block copolymer, the site where the cyclic molecule 20 encapsulates the linear polymer 10 preferably has a chain length longer than the thickness of the cyclic molecule 20. Here, the thickness of the cyclic molecule 20, as shown in schematic form in Figures 1(A) and (B), refers to the thickness T along the central axis Ax of the cyclic molecule 20. The site where the cyclic molecule 20 encapsulates the linear polymer 10 is a site made of a polymer of one type of monomer, one of two sites of a block copolymer, or one of three sites of a block copolymer.
[0062] The chain polymer 10 may have an ionizable group that ionizes in water or an aqueous solution. In one preferred embodiment, the chain polymer 10 has an ionizable group at or near at least one end. In another preferred embodiment, the chain polymer 10 has an ionizable group at at least one end. In another preferred embodiment, the chain polymer 10 has ionizable groups at both ends.
[0063] An example of an ionizable group is a carboxyl group (which ionizes to -COO - ), amino group (which ionizes to -NH 3+), sulfo group, phosphate group, trimethylamino chloride group, triethylamino chloride group, dimethylamino group, diethylamino group, methylamino group, ethylamino group, pyrrolidine group, pyrrole group, ethyleneimine group, piperidine group, pyridine group, pyrylium ion group, thiopyrylium ion group, hexamethyleneimine group, azatropyrylene group, imidazole group, pyrazole group, oxazole group, thiazole group, imidazoline group, morpholine group, thiazine group, triazole group, tetrazole group, pyridazine group, pyrimidine group, pyrazole The present invention is not limited to at least one selected from the group consisting of idine groups, indole groups, benzimidazole groups, purine groups, benzotriazole groups, quinoline groups, quinazoline groups, quinoxaline groups, pteridine groups, carbazole groups, porphyrin groups, chlorin groups, choline groups, adenine groups, guanine groups, cytosine groups, thymine groups, uracil groups, dissociated thiol groups, dissociated hydroxyl groups, azide groups, pyridine groups, carbamic acid, guanidine, sulfenes, ureas, thioureas, peracids, derivatives thereof, and analogs thereof.
[0064] The ionizable group is preferably at least one selected from the group consisting of a carboxyl group, an amino group, a sulfo group, a phosphate group, a trimethylamino chloride group, and a dimethylamino group, and more preferably at least one selected from the group consisting of a carboxyl group, an amino group, a trimethylamino chloride group, and a dimethylamino group.
[0065] Instead of the ionizable group, the chain polymer 10 may have a non-ionizable group. A conventionally known method can be used to introduce an ionizable group or a non-ionizable group into the chain polymer.
[0066] Examples of non-ionizable groups include isopropyl, sec-butyl, tert-butyl, neopentyl, isopentyl, sec-pentyl, 3-pentyl, tert-pentyl, cyclopentyl, pentene, hexyl, hexene, heptyl, heptene, octyl, octene, nonyl, nonene, decyl, decene, undecyl, undecene, dodecyl, dodecene, tridecyl, tridecene, tetradecyl, tetradecene, pentadecyl, pentadecene, hexadecyl, hexadecene, heptadecyl, heptadecene, octadecyl, oc ... the aryl, nonadecyl, nonadecene, eicosyl, eicosene, tetracosyl, tetracosene, triacontyl, triacontene and their isomers; 4-tert-butylbenzenesulfonyl, 2-mesitylenesulfonyl, methanesulfonyl, 2-nitrobenzenesulfonyl, 4-nitrobenzenesulfonyl, pentafluorobenzenesulfonyl, 2,4,6-triisopropylbenzenesulfonyl, p-toluenesulfonyl, non-ionized hydroxyl, heptafluorobutyroyl, pivaloyl, perfluorobenzoyl, non-ionized amino (-NH 2 ), a non-ionized carboxyl group (-COOH), and an isovaleryl group, but are not limited to these.
[0067] The non-ionizable group is preferably at least one selected from the group consisting of a non-ionizable hydroxy group, a heptafluorobutyroyl group, a perfluorobenzoyl group, and an isovaleryl group, and more preferably at least one selected from the group consisting of a perfluorobenzoyl group and an isovaleryl group.
[0068] Examples of the cyclic molecule 20 include, but are not limited to, cyclodextrin (e.g., α-cyclodextrin, β-cyclodextrin, γ-cyclodextrin), crown ethers, pillararenes, calixarenes, cyclophanes, cucurbiturils, and derivatives thereof. Examples of derivatives include, but are not limited to, methylated α-cyclodextrin, methylated β-cyclodextrin, methylated γ-cyclodextrin, hydroxypropylated α-cyclodextrin, hydroxypropylated β-cyclodextrin, hydroxypropylated γ-cyclodextrin, and the like.
[0069] The structure 1 may include one type of cyclic molecule 20, or may include two or more types of cyclic molecules 20. For example, when the structure 1 includes two or more types of cyclic molecules 20, the structure 1 may include a first cyclic molecule that is one of the compounds listed above, and a second cyclic molecule that is one of the compounds listed above and is different from the first cyclic molecule.
[0070] In this specification, the ratio of the cyclic molecules 20 contained in the pseudopolyrotaxane and / or polyrotaxane 2 is referred to as the inclusion rate.
[0071] The specified inclusion rate refers to an inclusion rate arithmetically defined from the linear polymer 10 and the cyclic molecule 20 contained in the pseudopolyrotaxane and / or polyrotaxane 2, and specifically, is defined from the length of the linear polymer 10 and the thickness T of the cyclic molecule 20.
[0072] The method for calculating the specified inclusion rate will be described using polyethylene glycol as the chain polymer 10 and α-cyclodextrin as the cyclic molecule.
[0073] It is known from molecular model calculations that the thickness of two repeating units of polyethylene glycol is the same as that of α-cyclodextrin. Therefore, the specified inclusion rate is 100% when the ratio of moles of α-cyclodextrin to repeating units of polyethylene glycol is 1:2.
[0074] The inclusion rate, which is the ratio of the cyclic molecules 24 contained in the pseudopolyrotaxane and / or polyrotaxane 2, can be determined by small angle X-ray scattering (SAXS) measurement of a dispersion of the obtained structure.
[0075] The inclusion rate of the pseudopolyrotaxane and / or polyrotaxane 2 is preferably 1 to 100%, more preferably 5 to 100%, further preferably 10 to 100%, and most preferably 20 to 100%, assuming that the specified inclusion rate is 100%.
[0076] In one preferred embodiment, to ensure a high occupancy of the cyclic molecules 20 in the structure, the linear polymer 10 has openings for three or more cyclic molecules 20 per linear polymer. To Incorporated into a skewer shape Be do.
[0077] Returning to FIG. 2, as long as the structure 1 according to the embodiment of the present invention can be formed, the structure 1 does not include components other than the pseudopolyrotaxane and / or polyrotaxane 2, i.e., the cyclic molecule 20 and the opening 24 of the cyclic molecule 20. To Incorporated into a skewer shape Be The cyclic molecule 20 may further include an additional substance 30 (see FIG. 6(F)) other than the chain polymer 10. Such a substance 30 may be a first substance that is included in the cyclic molecule 20, a second substance that is not included in the cyclic molecule 20, or both of them.
[0078] Examples of the first substance include a drug, a fluorescent substance, a chromogenic enzyme, and the like.
[0079] Examples of the above drugs include antitumor agents, antihypertensive agents, antihypertensive agents, antipsychotic agents, analgesics, antidepressants, antimanic agents, antianxiety agents, sedatives, antidementia drugs, hypnotics, antiepileptic agents, asthma treatment agents, anesthetics, antiarrhythmic agents, arthritis treatment agents, antispasmodics, ACE inhibitors, decongestants, antibiotics, antiangina agents, diuretics, antiParkinson's disease agents, bronchodilators, antidiuretics, diuretics, antihyperlipidemic agents, immunosuppressants, immunomodulators, antiemetics, antiinfective agents, antineoplastic agents, antifungal agents, antiviral agents, and antidiabetic agents. These include, but are not limited to, drugs for treating various conditions, antiallergies, antipyretics, antigout agents, antihistamines, antipruritics, bone regulating agents, cardiovascular agents, cholesterol lowering agents, antimalarials, antitussives, expectorants, mucolytics, dopaminergic agents, gastrointestinal agents, muscle relaxants, neuromuscular blocking agents, parasympathomimetics, stimulants, appetite suppressants, thyroid or antithyroid agents, hormones, antimigraine drugs, anti-obesity agents, anti-inflammatory agents, drugs for renal diseases, urinary system drugs, ophthalmic drugs, dermatological drugs, dental and oral drugs, etc. Drugs that are preferable in terms of ease of inclusion in the cyclic molecule 20 include, for example, steroids (particularly compounds having a basic skeleton of cyclopentahydrophenanthrene), anthracyclines, and fluorine-containing nucleosides. The above drugs include hydrocortisone, spironolactone, clofibrate, naproxen, adenine arabinoside, adenosine, ibuprofen, hydrochlorothiazide, acetylsalicylic acid, methyl salicylate, adamantane, azobenzene, anthracene, pyrene, polyphenylene vinylene, polyaniline, rhodamine, nile red, ethenzamide, prednisolone acetate, rebamipide, salbutamol, flurbiprofen, beclomethasone, piroxicam, ketoprofen, timoptol, dorzolamide, doxorubicin, isopropyl unoprostone, diphenylhydramine, diphenylhydramine, hydroxyzine, cetirizine, chloropheniramine, epinastine, levocabastine, levofloxacin, latanoprost, bimatoprost, tafluprost, timolol, bFGF (basic fibroblast growth factor: basic Fibroblast growthfactor), carboplatin, cisplatin, tegafur, nedaplatin, paclitaxel, pirarubicin, 5-fluorouracil, bleomycin, mitomycin, salicylic acid, flurbiprofen, dexamethasone, cytarabine, nimustine, dacarbazine, docetaxel, amphotericin, piroxicam, pancratistatin, phenytoin, adenine arabinoside, adenosine, diazepam, hydrochlorothiazide, daunorubicin, astemizole, beclomethasone, beclomethasone betamethasone, bendazac, bromazepam, celecoxib, chlorodiazepoxide, clovezem, clonazepam, coenzyme Q10, cortisone, curcumin, cyproterone acetate, fluocinolone acetate, flurazepam, flutamide, indomethacin, ketotifen, loratadine, lorazepam, medazepam, meloxipam, natamycin, nimesulide, nimetazepam, nitrazepam, nystatin, prednisolone, progesterone, risperidone, salbutamol, sildenafil , telmisartan, testosterone, triamcinolone, felbinac, adrenal extract, heparinoids, loxoprofen sodium hydrate, diclofenac sodium, ketoprofen, prednisolone acetate, fluocinolone, lotepredenol, difluprednate, triamcinolone, rimexolone, dexamethasone, fluorometholone, sodium metasulfobenzoate, betamethasone sodium phosphate, dexamethasone sodium phosphate, cefmenol cimetidine, ofloxacin, chloramphenicol, donepezil; and pharma- ceutical acceptable salts of any of the above compounds (e.g., salbutamol sulfate, doxorubicin hydrochloride, nimustine hydrochloride, dorzolamide hydrochloride, nilhydramine hydrochloride, hydroxyzine hydrochloride, cetirizine hydrochloride, chlorpheniramine maleate, epinastine hydrochloride, levocabastine hydrochloride, timolol maleate, beclomethasone hydrochloride, cefmenoxime hydrochloride, donepezil hydrochloride), and the like, but are not limited to these.
[0080] Examples of the fluorescent substance include, but are not limited to, rhodamine, Nile red, poly-L-lysine-fluorescein isothiocyanate (FITC), uranine, coumarin, Cy2, Cy3, Cy5, and the like.
[0081] Examples of the color-developing enzyme include, but are not limited to, horseradish peroxidase (HRP), alkaline phosphatase, β-galactosidase, glucose oxidase, luciferase, and the like.
[0082] An example of the second substance is a polymer that is not included in the cyclic molecule 20.
[0083] Examples of polymers that are not included in the cyclic molecule 20 include polymers such as polystyrene, polyvinylpyridine, polypyridine, polyphenylene, polyacrylamide, polyacrylic acid, polymethacrylic acid, polyvinyl alcohol, polyamide, polyester, polyimide, polybenzoxazole, polyvinyl chloride, polyolefin (polyethylene, polypropylene, etc.), polysilane, polysiloxane, etc.; biopolymers such as DNA and proteins having 50 or more amino acids bound thereto; biomolecules such as peptides having less than 50 amino acids bound thereto; inorganic nanomaterials such as silica nanoparticles, titanium oxide nanoparticles, and silicon nanoparticles; carbon materials such as fullerene, carbon nanotubes, graphene, graphite, and carbon quantum dots; metal and inorganic nanoparticles such as gold nanoparticles, perovskite quantum dots, CdSeS / ZnS quantum dots, iron oxide nanoparticles, and nanodiamonds; and cell adhesion molecules such as fibronectin, collagen, cadherin, integrin, laminin, fibrinogen, and polylysine, but are not limited to these.
[0084] The substance 30 may be bonded to the linear polymer 10, bonded to the cyclic molecule 20, held in the space 4 between a plurality of pseudo-polyrotaxanes and / or polyrotaxanes 2 (i.e., between a plurality of columns, particularly two, three, or four columns, which are columnar structures made of pseudo-polyrotaxanes and / or polyrotaxanes) (illustrated in FIG. 2), accommodated in an opening 24 partitioned and formed by one cyclic molecule 20 (illustrated in FIG. 1(B)), or accommodated in a space 6 partitioned and formed by a plurality of cyclic molecules 20 (illustrated in FIG. 1(B) and FIG. 2). When the substance 30 is bonded to the linear polymer 10, it is preferably bonded to both ends or one end of the linear polymer 10 or in the vicinity thereof, but it may be bonded to another site of the linear polymer 10. In addition, it is preferable that the linear polymer 10 is not accommodated in the space 6 partitioned and formed by a plurality of cyclic molecules 20 in terms of accommodating the substance 30, but molecules other than the substance 30, including the linear polymer 10, may be accommodated.
[0085] The size of the space 4 between multiple pseudo-polyrotaxanes and / or polyrotaxanes 2, the size of the opening 24 partitioned by one cyclic molecule 20, and the size of the space 6 partitioned by multiple cyclic molecules 20 can be appropriately changed by changing the length of the chain polymer 10, the hydrophilicity and hydrophobicity of the chain polymer 10, the type of cyclic molecule 20, etc., so the size of the space 4, the size of the opening 24, and / or the size of the space 6 can be appropriately changed depending on the size of the substance 30 to be accommodated.
[0086] Since the structure 1 according to the embodiment of the present invention is thicker than a conventional single-layer nanosheet, one structure can incorporate a large amount of a substance 30 such as a drug. Therefore, the structure 1 according to the embodiment of the present invention can function as a vehicle for the drug and can extend the sustained release time of the drug.
[0087] Furthermore, the structure 1 according to the embodiment of the present invention is made of molecules that are highly safe for the body, and is therefore suitable for use in the body.
[0088] Furthermore, the structure 1 according to the embodiment of the present invention can be produced more quickly by using the short chain polymer 10 as a raw material, and this allows reduction in energy and cost.
[0089] As shown in Figures 6(A)-(F), the chain polymer 10 and the cyclic molecule 20 in the structure 1 can have various configurations as long as the structure 1 as an aggregate is maintained, so long as the intended function of the structure 1 can be exerted. For example, in FIG. 6(A), a plurality of (six in the figure) cyclic molecules 20 form a column, and one chain polymer 10 is accommodated inside a space 6 formed by a series of openings 24 of the cyclic molecules 20. Although the single chain polymer 10 extends across the openings 24 of the cyclic molecules 20, both ends of the chain polymer 10 do not reach both ends of the column made of the cyclic molecules 20, and the chain polymer 10 is accommodated in the space 6. The column made of the cyclic molecules 20 can also be referred to as a pile or stack made of the cyclic molecules 20. The openings 24 of the cyclic molecules 20 or the space 6 formed by the cyclic molecules 20 may or may not accommodate a substance 30.
[0090] In Figure 6 (B), two chain polymers 10 are contained inside the space 6, and the two chain polymers 10 extend across the openings 24 of the multiple cyclic molecules 20, with both ends of the chain polymer 10 reaching both ends of the column made up of the multiple cyclic molecules 20, and the total height of the multiple cyclic molecules 20 constituting one pseudopolyrotaxane and / or polyrotaxane 2 roughly corresponds to the total length of the polymer 10.
[0091] 6(C), both ends of the chain polymer 10 slightly protrude outward from the circular molecule 20. The chain polymer 10 has a modifying group 18 at one end of its main body 12.
[0092] In FIG. 6(D), one end 14 of the chain polymer 10 is accommodated in the space 6 and the other end 16 protrudes slightly outside the cyclic molecule 20.
[0093] 6(E), one chain polymer 10 is accommodated in the space 6, and this chain polymer 10 extends into the openings 24 of the four cyclic molecules 20, but does not extend into the openings 24 of the top and bottom cyclic molecules 20. In other words, the length of the chain polymer 10 is short, being half or less of the length of the space 6 (i.e., the total height of the multiple cyclic molecules 20).
[0094] 6(F) shows only a column made up of a plurality of cyclic molecules 20, without a chain polymer 10. In this embodiment, a substance 30 is contained in the space 6 formed by the plurality of cyclic molecules 20.
[0095] In one preferred embodiment, all of the columns of the cyclic molecules 20 in the structure 1 are provided with the linear polymer 10. In another preferred embodiment, among the columns of the cyclic molecules 20 in the structure 1, some of the columns are provided with the linear polymer 10, and the remaining some of the columns are not provided with the linear polymer 10.
[0096] As described above, the size of space 4, the size of opening 24, and / or the size of space 6 can be designed and adjusted as appropriate according to the size of substance 30 to be contained. In addition, the occupancy rate of space 4, the size of opening 24, and / or the size of space 6 in structure 1 can also be designed and adjusted as appropriate. Therefore, for example, when substance 30 is a drug, a desired amount of the drug can be contained in space 4, opening 24, and / or space 6 of structure 1, and structure 1 can function as a drug encapsulation body or a drug release control carrier. The amount of the substance 30 in the structure 1 can be measured by absorbance measurement. For example, a calibration curve of substance concentration-absorbance at a predetermined wavelength of a solution of a substance 30 of known concentration dissolved in a solvent is measured in advance. A predetermined amount of the structure 1 is dissolved in the same solvent, and the absorbance is measured to obtain an absorbance value at a predetermined wavelength. The concentration of the substance is calculated from the obtained absorbance value and the calibration curve, and the amount of the substance 30 in the structure 1 is calculated. In an embodiment, the amount of the substance 30 in the structure 1 is 0.0001 mass% or more, and more specifically, may be 0.001 to 11 mass%, but is not limited thereto. When referring to the substance 30 in the structure 1 or the substance 30 encapsulated in the structure 1, the substance 30 includes a substance contained in the space 6 partitioned and formed by the cyclic molecules 20, a substance 30 that is not encapsulated in the cyclic molecules 20 and exists between the multiple cyclic molecules 20, and a substance 30 that is not encapsulated in the cyclic molecules 20 and is attached to the outer surface of the structure 1 rather than between the multiple cyclic molecules 20.
[0097] A preferred structure 1 of the present invention has excellent adhesion to a solid substrate. The solid substrate may be a non-living solid substrate or a living organism. A plate-shaped substrate is called a substrate. Examples of non-living solid substrates include solid substrates made of inorganic materials and solid substrates made of organic materials. Examples of solid substrates made of inorganic materials include, but are not limited to, glass, metal, metal oxide, silicon, quartz, zirconia, etc. Examples of solid substrates made of organic materials include, but are not limited to, synthetic resins, biopolymers, etc. Examples of the organism include a part of a biological tissue.
[0098] Furthermore, the structure 1 can be widely used not only in medicine but also in the fields of bioimaging, food, cosmetics, industrial chemistry, etc., as an inclusion body or release control carrier for the substance 30. The structure 1 according to the embodiment of the present invention is applied in a wide range of fields, such as a drug delivery material, a reagent for bioimaging, a masking material for food molecules (particularly volatile molecules such as odor molecules), a hair care material, a coating material, a paint, an adhesive, a wound healing material, an artificial living body replacement material, a packaging material, a rubber material, an oral care material such as mouthwash, a base for supplements, a highly functional beverage, and an aggregation control material for cells, algae, etc.
[0099] As shown in FIG. 7, in one specific embodiment, the structure 1 has the basic structure of the embodiment shown in FIG. 2 and further has one or more through holes 8 (one in the figure) penetrating the structure 1. The size of each through hole 8 is not limited, but it is preferable that the through hole 8 occupies a space larger than the volume occupied by one pseudopolyrotaxane and / or polyrotaxane 2. The one pseudopolyrotaxane and / or polyrotaxane 2 may be any pseudopolyrotaxane and / or polyrotaxane 2 in the structure 1, but is, for example, the pseudopolyrotaxane and / or polyrotaxane with the largest volume. The through hole 1 can be formed by attaching the structure 1 of the embodiment of the present invention to a substrate and washing it with water or an aqueous solution at a constant temperature for a certain time. The washing temperature is not limited, but is, for example, 5 to 45° C., and preferably 15 to 30° C. The washing time is not limited, but is, for example, 10 to 60 seconds.
[0100] Next, a method for producing the structure 1 will be described.
[0101] Methods I and II for manufacturing the structure of the embodiment of the invention are provided. <Manufacturing method I> The production method I is a) preparing a linear polymer 10; b) providing a cyclic molecule 20; and c) mixing the chain polymer 10 and the cyclic molecule 20 in water or an aqueous solution; To Chain Polymer 10 but It is possible to obtain a structure having a plurality of pseudo-polyrotaxanes that are encapsulated in a skewered shape, in which at least a portion of the plurality of pseudo-polyrotaxanes and / or polyrotaxanes are arranged in series with one another.
[0102] In step c), the multiple pseudopolyrotaxanes and / or polyrotaxanes contained in the column, both ends of which are made of multiple cyclic molecules, interact with each other, and at least a portion of the multiple pseudopolyrotaxanes and / or polyrotaxanes are arranged in series with each other.
[0103] The "chain polymer 10" and the "cyclic molecule 20" are as described above.
[0104] <Step a)> Step a) is a step of preparing a chain polymer 10 having a chain polymer 10 .
[0105] Here, the chain polymer 10 may be commercially available or may be prepared. When "chain polymer 10" is prepared, it can be obtained by the methods described in the following documents 1 to 4. Reference 1: Hillmyer, MA et al., Macromolecules 1996, 29(22) 6994-7002. Reference 2: Ding, JF et al., Eur Polym J 1991, 27(9), 901-905. Reference 3: Allegaier, J. et al., Macromolecules 2007, 40(3), 518-525.Reference 4:Malik, MI et al., Eur Po.ym J 2009,45(3), 899-910.
[0106] <Step b)> Step b) is a step of preparing a cyclic molecule 20 .
[0107] In this step, a commercially available cyclic molecule may be purchased or prepared. When preparing a derivative, it can be obtained by a method described in, for example, literature 5: Khan, AR et al., Chem Rev 1998, 98(5), 1977-1996.
[0108] It should be noted that step b) may be performed before step c), i.e. step b) does not have to be performed after step a), and steps a) and b) can be performed separately.
[0109] <Process c)> Step c) is a step of mixing the linear polymer 10 and the cyclic molecule 20 in water or an aqueous solution. There are no particular limitations on the water or aqueous solution as long as it is a solvent in which at least one of the cyclic molecule 20 and the linear polymer 10 can be dissolved.
[0110] Specific examples of the water or aqueous solution used in step c) include pure water, an aqueous alcohol solution, an aqueous acid solution, an aqueous alkaline solution, a buffer solution, a culture medium, and a plasma solution, but are not limited to these.
[0111] By carrying out the above steps a) to c), the above structure can be obtained.
[0112] The above-mentioned production method may have steps other than the above steps a) to c). For example, the steps other than the above steps a) to c) may include, but are not limited to, a preparation step of the above-mentioned "chain polymer 10" before the step a), a purification step of the structure after the step d), and inclusion of the cyclic molecule and the first substance that may be provided before the step a) or synthesis of the pseudopolyrotaxane or polyrotaxane. Furthermore, in the case where the structure has the above-mentioned substance 30, the manufacturing method of the present invention may include a step for introducing the substance 30 into the structure 1. To introduce the substance 30 into the structure 1, the chain polymer 10 and the substance 30 such as a drug are first mixed in water or an aqueous solution to dissolve or disperse them. If the substance 30 contains a substance that is poorly soluble in water, the mixed solution may be subjected to ultrasonic waves. Then, the cyclic molecule 20 is added to the mixed solution and shaken until it is sufficiently dissolved or dispersed, thereby obtaining the structure 1 incorporating the substance 30. Then, the suspension containing the structure 1 is centrifuged to precipitate the structure 1, the precipitate is washed with an aqueous solution or water containing the cyclic molecule 20, centrifuged several times, the supernatant is removed, and the structure 1 incorporating the substance 30 is obtained.
[0113] Furthermore, the method may further include, after the step c), a step of modifying a part of the pseudo-polyrotaxane of the obtained structure.
[0114] The modification step may be a step of introducing a first substituent into the chain polymer 10, for example, into the end of the chain polymer 10. The first substituent may be a blocking group having a function of blocking the cyclic molecule 20 so that it does not leave, or may have other functions, so long as a structure is obtained. The first substituent may have any combination of these functions, or may have all of these functions.
[0115] For example, groups having a blocking effect include an adamantane group, a neopentyl group, an isopentyl group, a sec-pentyl group, a 3-pentyl group, a tert-pentyl group, a cyclopentyl group, a pentene group, a hexyl group, a hexene group, a heptyl group, a heptene group, an octyl group, an octene group, a nonyl group, a nonene group, a decyl group, a decene group, a one-decyl group, an undecene group, a dodecyl group, a dodecene group, a tridecyl group, a tridecene group, a tetradecyl ... Examples of such alkyl groups include, but are not limited to, a ladecyl group, a tetradecene group, a pentadecyl group, a pentadecene group, a hexadecyl group, a hexadecene group, a heptadecyl group, a heptadecene group, an octadecyl group, an octadecene group, a nonadecyl group, a nonadecene group, an eicosyl group, an eicosene group, a heicosyl group, a heicosene group, a tetracosyl group, a tetracosene group, a triacontyl group, a triacontene group, and isomers thereof.
[0116] As other functions, for example, groups having the function of an ionizable group, such as folic acid, biotin, fluorescein, oligopeptides such as RGD and GRGDS, and groups derived from monoclonal antibodies such as rituximab, bevacizumab, tocilizumab and imbriximab, may be introduced. For example, when introducing a group derived from folic acid, the resulting isolated sheet and folic acid can be reacted in the presence of a condensing agent such as DMT / MM (4-(4,6-dimethoxy-1,3,5-triazin-2-yl)-4-methylmorpholinium chloride), DCC (N,N'-dicyclohexylcarbodiimide), EDC (1-(3-dimethylaminopropyl)-3-ethylcarbodiimide), BOP (benzotriazol-1-yloxytrisdimethylaminophosphonium salt), PyBOP ((benzotriazol-1-yloxy)tripyrrolidinophosphonium hexafluorophosphate), or HATU (0-(7-azabenzotriazol-1-yl)-N,N,N',N'-tetramethyluronium hexafluorophosphate).
[0117] The modification step may be a step of introducing a second substituent into the cyclic molecule 20, so long as a structure is obtained.
[0118] <Manufacturing method II> Production method II is a') preparing a linear polymer 10; b) providing a cyclic molecule 20; c') mixing the chain polymer 10 and the cyclic molecule 20 in water or an aqueous solution to obtain a pseudopolyrotaxane; d) introducing substituents into both ends of at least a part of the chain polymer 10 to form a chain polymer 10; e) introducing blocking groups into both ends of the chain polymer 10 of the pseudopolyrotaxane and / or at least a portion of the chain polymer 10; f) mixing the obtained pseudopolyrotaxane and / or polyrotaxane in water or an aqueous solution; By this manufacturing method, the opening of the cyclic molecule 20 To Chain Polymer 10 but It is possible to obtain a structure having a plurality of pseudo-polyrotaxanes that are encapsulated in a skewered shape, in which at least a portion of the plurality of pseudo-polyrotaxanes and / or polyrotaxanes are arranged in series with one another.
[0119] In step f), the multiple pseudopolyrotaxanes and / or polyrotaxanes contained in the column, both ends of which are made of multiple cyclic molecules, interact with each other, and at least a portion of the multiple pseudopolyrotaxanes and / or polyrotaxanes are arranged in series with each other.
[0120] Here, in step a'), the "chain polymer 10" described in the above step a) can be used. In step b), the process is the same as the above-mentioned "step b"
[0121] Step c') is a step of mixing the linear polymer 10 and the cyclic molecule 20 in water or an aqueous solution, similar to the above step c), thereby obtaining a pseudo-polyrotaxane. As for the water or aqueous solution, as described in step c), there is no particular limitation as long as it is a solvent in which at least one of the cyclic molecule 20 and the linear polymer 10 can be dissolved.
[0122] Specific examples of the water or aqueous solution used in step c) include pure water, an aqueous alcohol solution, an aqueous acid solution, an aqueous alkaline solution, a buffer solution, a culture medium, and plasma, but are not limited to these.
[0123] Step d) is a step of introducing substituents into both ends of at least a part of the chain polymer 10 to form the chain polymer 10.
[0124] As a non-limiting example of the introduction of the above-mentioned substituent, a carboxylic acid can be introduced by an oxidation reaction using hypochlorous acid and 2,2,6,6-tetramethylpiperidine 1-oxyl. An amino group can be introduced by a coupling reaction using 1'-carbonyldiimidazole and ethylenediamine. A sulfo group can be introduced by reacting 1,3-propane sultone with the chain polymer 10.
[0125] Non-limiting examples of the introduction of other substituents include condensation reactions such as esterification and amidation using condensing agents such as DMT / MM (4-(4,6-dimethoxy-1,3,5-triazin-2-yl)-4-methylmorpholinium chloride), DCC (N,N'-dicyclohexylcarbodiimide), EDC (1-(3-dimethylaminopropyl)-3-ethylcarbodiimide), BOP (benzotriazol-1-yloxy-trisdimethylaminophosphonium salt), PyBOP ((benzotriazol-1-yloxy)tripyrrolidinophosphonium hexafluorophosphate), and HATU (0-(7-dibenzotriazol-1-yl)-N,N,N',N'-tetramethyluronium hexafluorophosphate), but are not limited thereto.
[0126] Step e) is a step of introducing a so-called blocking group, which reduces the elimination rate of the cyclic molecule 20. This step can be performed using a conventionally known method, for example, the step described in Harada et al., Nature, 1992, 356, 325-327. As for the blocking group, a blocking group that can be used for a conventionally known polyrotaxane can be used. For example, the blocking group described in M. Okada et al., J Polym. Sci. A: Polym. Chem, 2000, 38, 4839-4849 can be used.
[0127] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these. EXAMPLES
[0128] Example 1: Formation of a structure using γ-CD γ-CD was obtained from CycloChem Co., Ltd. The linear polymer PEO2k (numbers indicate weight-average molecular weight) was purchased from Sigma Aldrich and Wako Pure Chemical Industries.
[0129] The pseudopolyrotaxane (PPR) was prepared as follows: γ-CD was dissolved in deionized water (pH about 7) at 23±1°C. The γ-CD concentration was 0.12 g mL -1 0.25g of PEO2k was added to 8.4mL of γ-CD aqueous solution. The mixed solution was stirred by vortex for 1 minute. The solution was then placed on a shaker and aged. Within a day, the precipitate and liquid layer separated, and the complex formation was almost complete. The sample was named PPR_EO400.
[0130] Samples for scanning electron microscopy (SEM) were prepared by immersing silicon oxide substrates in aqueous dispersions of polyrotaxanes. SEM observations were performed with a JEOL JSM-7800F instrument. In-situ crystal growth induced by complex formation was recorded with a Nikon ECLIPSE Ts2R phase contrast microscope equipped with a Nikon DS-Fi3 camera.
[0131] Figure 8(A) shows a photograph of the formation of PPR_EO400 observed with the naked eye. As the structure formed, the solution gradually became cloudy. Figures 8(B) and (C) show optical microscope and SEM photographs of PPR_EO400. It was confirmed that rod-shaped structures were formed.
[0132] Example 2 Control of the shape of the structure based on the length of the chain polymer γ-CD was obtained from CycloChem Co., Ltd. Linear polymers PEO400 (numbers indicate weight-average molecular weight), PEO2k, PEO4k, PEO6k, and PEO20k were purchased from Sigma Aldrich and Wako Pure Chemical Industries.
[0133] The preparation method of pseudopolyrotaxane (PPR) was the same as in Example 1. The prepared samples were named PPR_EO400, PEO_EO2k, PPR_EO4k, PPR_EO6k, and PPR_EO20k, respectively.
[0134] SEM observation was performed under the same experimental conditions as in Example 1. WAXS measurements were performed by injecting an aqueous dispersion of polyrotaxane into a glass capillary (WJM-Glass / Muller GmbH Boro-Silicate capillary: φ=2.0 × length=80 mm) and drying the sample at room temperature for one day, after which the particles attached to the glass wall were used as targets.
[0135] The SEM observations were performed using the same equipment as in Example 1. WAXS experiments were performed using a Rigaku NANOPIX instrument equipped with a Hypix-3000 detector. The sample-to-detector distance was calibrated against the diffraction peak of silver behenate.
[0136] SEM photographs of PPR_EO400, PPR_EO4k, PPR_EO6k, and PPR_EO20k are shown in Figures 9(A) to (D), respectively. It was confirmed that PPR_EO400 formed rod-like structures, PPR_EO4k formed cube-like structures, and PPR_EO6k and PPR_EO20k formed sheet-like structures. When the crystal structures were analyzed by WAXS, tetragonal crystals were formed in all samples. The crystal planes corresponding to the peaks are illustrated in Figure 10.
[0137] Example 3 Effect of hydrophilicity / hydrophobicity of linear polymers γ-CD was obtained from CycloChem Co., Ltd. Linear polymers PPO400 (numbers indicate weight-average molecular weight), PPO2k, and PPO4k were purchased from Sigma Aldrich and Wako Pure Chemical Industries.
[0138] The preparation method of pseudopolyrotaxane (PPR) was the same as in Example 1. The prepared samples were named PPR_PO400, PPR_PO2k, and PPR_PO4k, respectively.
[0139] SEM observation was performed under the same experimental conditions as in Example 1. The SEM images of each are shown in FIG. 11. As the molecular weight increased, the structure changed from a rod-like structure to a sheet-like structure. However, in PPR_PO4k, an amorphous structure was formed. When the molecular weight of the linear polymer increases, the linear polymer needs to fold, but if the linear polymer is hydrophobic, hydrophobic aggregation occurs and an amorphous structure is formed. On the other hand, if the linear polymer is hydrophilic, hydrophobic aggregation does not occur, and a structure with a regular shape is formed.
[0140] Example 4 Formation of an ultra-thin structure when a triblock copolymer is used as a chain polymer γ-CD was obtained from CycloChem Co., Ltd. Linear triblock polymer EO 4 PO 56 EO 4 (Subscripts are unit numbers), EO 25 PO 56 EO 25 , E.O. 147 PO 56 EO 147 was purchased from Sigma Aldrich.
[0141] The preparation method of pseudopolyrotaxane (PPR) was the same as in Example 1. The prepared samples were each named PPR_EO 4 PO 56 EO 4 , PPR_EO 25 PO 56 EO 25 , and PPR_EO 147 PO 56 EO 147 and named it.
[0142] Samples for atomic force microscopy (AFM) and SEM observations were prepared by immersing silicon oxide substrates in an aqueous dispersion of polyrotaxane. AFM experiments were carried out at ambient conditions using a Bruker Nano Multimode 8 instrument operated in tapping mode. The resonant frequency was approximately 300 Hz and the spring constant was 40 Nm. -1A silicon cantilever tip (Bruker RTESPA-300) doped with 1000 g of antimony was used. SAXS measurements were performed by injecting an aqueous dispersion of polyrotaxane into a glass capillary (WJM-Glass / Muller GmbH Boro-Silicate capillary: φ=2.0×length=80 mm). WAXS experiments were performed under the same conditions as in Example 2.
[0143] The SEM images of each are shown in Figure 12 (A), (B), and (C). 4 PO 56 EO 4 and PPR_EO 25 PO 56 EO 25 In the case of PPR_EO, a relatively thick sheet-like structure was formed. 147 PO 56 EO 147 An ultra-thin structure was formed. The WAXS profile (Fig. 12(D)) showed that tetragonal crystals were formed. 147 PO 56 EO 147 The thickness of the layer was measured by AFM and found to be 33 nm (FIG. 12(E)).
[0144] Example 5: Production of nanosheets with through holes PPR_EO created in Example 4 147 PO 56 EO 147 After the substrate was attached to a silicon oxide substrate, it was washed with water for 20 seconds and observed under SEM (Figure 13). It was confirmed that a nanosheet structure with through holes had been formed.
[0145] Example 6 Formation of a microstructure using α-CD α-CD was purchased from Nihon Shokuhin Kako Co., Ltd. The linear polymer PEO400 (numbers indicate weight-average molecular weight) was purchased from Sigma Aldrich.
[0146] The pseudopolyrotaxane (PPR) was prepared as follows: α-CD was dissolved in deionized water (pH about 7) at 23±1°C. The α-CD concentration was 0.12 g mL -10.25g of PEO400 was added to 8.4mL of α-CD aqueous solution. The mixture was stirred by vortex for 1 minute. The solution was then placed on a shaker and aged. Within a day, the precipitate and liquid layers separated, and the complex formation was almost complete. SEM observation (FIG. 14) was performed in the same manner as in Example 1. It was confirmed that a hexagonal columnar microstructure was formed.
[0147] Example 7 Formation of a microstructure using β-CD β-CD was purchased from Fujifilm Wako Pure Chemical Industries, Ltd. Poly(propylene glycol) bis(2-aminopropyl ether) 2k (numbers indicate weight average molecular weight, NH 2 PPO2k) was purchased from Sigma Aldrich.
[0148] The pseudopolyrotaxane (PPR) was prepared as follows. β-CD was dissolved in deionized water (pH about 7) at 23±1°C. The β-CD concentration was 18 mg / mL. -1 1 mg of NH 2 PPO2k was added to 1.0 mL of β-CD aqueous solution. The mixed solution was stirred by vortex for 1 min. The solution was then placed on a shaker and aged. After one week, the precipitate and liquid layer separated, and the complex formation was almost complete. The sample was then mixed with βCD / NH 2 We named it PPO2k.
[0149] SEM observation (FIG. 15) was performed in the same manner as in Example 1. It was confirmed that a diamond-shaped microstructure was formed.
[0150] Example 8 Microstructure formation using axis molecules other than PEO and PPO β-CD was purchased from Fujifilm Wako Pure Chemical Co., Ltd. γ-CD was obtained from CycloChem Co., Ltd. Polytetrahydrofuran 1.4k (numbers indicate weight average molecular weight, PTHF1.4k) was purchased from Wako Pure Chemical Industries and Sigma Aldrich. Silanol-terminated polydimethylsiloxane 700-1500 (PDMS1.1k) and PDMS2k-3.5k (PDMS2.75k) were purchased from AZMAX Corporation. PDMS1000-PEO2100 diblock copolymer (PDMS1k-PEO2.1) was purchased from Polymer Source.
[0151] The PPR consisting of β-CD was prepared as follows: β-CD was dissolved in deionized water (pH about 7) at 23±1°C. The β-CD concentration was 18 mg / mL. -1 1 mg of PDMS1.1k and NH 2 PPO2k was added to 1.0 mL of β-CD aqueous solution. The mixed solution was stirred by vortex for 1 minute. The solution was then placed on a shaker and aged. After one week, the precipitate and liquid layer separated, and the complex formation was almost complete. The sample was named βCD / PDMS1.1k.
[0152] The PPR consisting of γ-CD was prepared as follows: γ-CD was dissolved in deionized water (pH about 7) at 23±1°C. The γ-CD concentration was 0.12 g mL -1 The mixture was stirred for 1 min by vortexing. The solution was then placed on a shaker and aged. Within a day, the precipitate and liquid layer separated, and the complex formation was almost complete. The samples are named γ-CD / PDMS2.75k, γ-CD / PDMS1k-PEO2.1, and γ-CD / PTHF1.4k, respectively.
[0153] SEM observation was performed in the same manner as in Example 1. SEM images of βCD / PDMS1.1k, γ-CD / PDMS2.75k, γ-CD / PDMS1k-PEO2.1, and γ-CD / PTHF1.4k are shown in Figures 16(A) to (D). It was confirmed that a diamond-shaped microstructure was formed in βCD / PDMS1.1k, and a tetragonal-shaped microstructure was formed in γ-CD / PDMS2.75k, γ-CD / PDMS1k-PEO2.1, and γ-CD / PTHF1.4k.
[0154] Example 9 Formation of a Tent-Like Structure γ-CD was obtained from CycloChem Co., Ltd. Perfluorohexanoic acid (C 5 F 11 -COOH) was purchased from Tokyo Chemical Industry Co., Ltd.
[0155] The PPR consisting of γ-CD was prepared as follows: γ-CD was dissolved in deionized water (pH about 7) at 23±1°C. The γ-CD concentration was 0.12 g mL -1 0.14g of C 5 F 11 -COOH was added to 1.25 mL of γ-CD aqueous solution. The mixed solution was stirred by vortex for 1 min. The solution was then placed on a shaker and aged. Within a day, the precipitate and liquid layer separated, and the complex formation was almost complete. The sample was 5 F 11 Name it -COOH.
[0156] SEM observation was performed in the same manner as in Example 1. 5 F 11 The SEM image of -COOH is shown in Figure 17. It was confirmed that a tent-shaped structure (facing down) was formed.
[0157] Example 10 Formation of a polyhedral microstructure α-CD was purchased from Nihon Shokuhin Kako Co., Ltd. Sodium hexadecyl sulfonate (C 16 H 33 SO 3 Na) was purchased from Tokyo Chemical Industry Co., Ltd.
[0158] The pseudopolyrotaxane (PPR) was prepared as follows: α-CD was dissolved in deionized water (pH about 7) at 23±1°C. The α-CD concentration was 0.12 g mL -1 0.12g of C 16 H 33 SO 3 Na was added to 2.5 mL of α-CD aqueous solution. The mixed solution was stirred by vortex for 1 minute. The solution was then placed on a shaker and aged. Within a day, the precipitate and liquid layer separated, and the complex formation was almost complete. The sample was then transferred to α-CD / C 16 H 33 SO 3 Name it Na.
[0159] SEM observation was performed in the same manner as in Example 1. 16 H 33 SO 3 The SEM image of Na is shown in Figure 18. The formation of a polyhedral microstructure was confirmed.
[0160] Example 11 Formation of a sheet-like microstructure α-CD was purchased from Nihon Shokuhin Kako Co., Ltd. Sodium 1-nonanesulfonate (C 9 H 19 SO 3 Na) was purchased from Tokyo Chemical Industry Co., Ltd.
[0161] The pseudopolyrotaxane (PPR) was prepared as follows: α-CD was dissolved in deionized water (pH about 7) at 23±1°C. The α-CD concentration was 0.12 g mL -1 86mg of C 9 H 19 SO 3 Na was added to 2.5 mL of α-CD aqueous solution. The mixed solution was stirred by vortex for 1 minute. The solution was then placed on a shaker and aged. Within a day, the precipitate and liquid layer separated, and the complex formation was almost complete. The sample was then transferred to α-CD / C 9 H 19 SO 3 Name it Na.
[0162] A sample for structural analysis was prepared in the same manner as in Example 1. 9 H 19 SO 3 The results of SEM observation of Na are shown in Figure 19 ((A) is low magnification, (B) is high magnification). The formation of a sheet-like microstructure was confirmed.
[0163] Example 12 Formation of hollow spherical structures α-CD was purchased from Nihon Shokuhin Kako Co., Ltd. Linear triblock polymer EO 37 PO 56 EO 37 (subscripts indicate unit numbers) were purchased from Sigma Aldrich.
[0164] The pseudopolyrotaxane (PPR) was prepared as follows: α-CD was dissolved in deionized water (pH about 7) at 23±1°C. The α-CD concentration was 0.12 g mL -1 0.25g of EO 37 PO 56 EO 37 was added to 8.4 mL of α-CD aqueous solution. The mixed solution was stirred by vortex for 1 min. The solution was then placed on a shaker and aged. Within a day, the precipitate and liquid layer separated, and the complex formation was almost complete. The sample was then mixed with α-CD / EO 37 PO 56 EO 37 and named it.
[0165] A sample for structural analysis was prepared in the same manner as in Example 1. 37 PO 56 EO 37 The results of SEM observation are shown in Figure 20 ((A) is low magnification, (B) is medium magnification, and (C) is high magnification). The formation of hollow spherical structures was confirmed.
[0166] Example 13 Formation of hollow columnar structures β-CD was purchased from Fujifilm Wako Pure Chemical Industries, Ltd. Polyethylene glycol monooleyl ether (n = 20, C18EO20) was purchased from Tokyo Chemical Industry Co., Ltd.
[0167] PPR was prepared as follows: β-CD was dissolved in deionized water (pH about 7) at 23±1°C. The β-CD concentration was 18 mg / mL. -1 81 mg of C18EO20 was added to 5.0 mL of β-CD aqueous solution. The mixture was stirred by vortex for 1 min. The solution was then placed on a shaker and aged. Within a day, the precipitate and liquid layer separated, and the complex formation was almost complete. The sample was named βCD / C18EO20.
[0168] Observation with an optical microscope was carried out in the same manner as in Example 1. The results of the optical microscope observation of βCD / C18EO20 are shown in Figure 21. The formation of hollow columnar structures was confirmed.
[0169] Example 14 Encapsulation of anticancer drugs in microstructures γ-CD was obtained from CycloChem Co., Ltd. Polyethylene oxide 4.6k (hereinafter PEO4.6k, weight average molecular weight 4.6k) was purchased from Sigma Aldrich. Doxorubicin hydrochloride was purchased from Fujifilm Wako Pure Chemical Industries.
[0170] The preparation of anticancer drug-encapsulated microstructures is as follows. 120 mg of γ-CD and 45 mg of doxorubicin were dissolved in 1 mL of deionized water (pH about 7) at 23 ± 1 °C. The concentration of γ-CD was 120 mg / mL, and the concentration of doxorubicin hydrochloride was 4.5 mg / mL. 30 mg of PEG4600 was added to the 1 mL of the prepared aqueous solution of γ-CD and doxorubicin hydrochloride. The mixed solution was stirred with a vortex for 1 minute. The solution was then placed on a shaker and aged. Within one day, the precipitate and liquid layer separated, and the complex formation was almost complete. The sample was named Dox-PPR_EO4.6k.
[0171] Microscopic observation was performed using a Nikon ECLIPSE Ts2R equipped with a Nikon DS-Fi3 camera, and fluorescence observation was performed using light with a wavelength of 470 nm as the excitation light.
[0172] The results of phase contrast and fluorescence microscopy of Dox-PPR_EO4.6k are shown in Figure 22 (A) and (B). The phase contrast microscopy confirmed that the microstructure was formed. The fluorescence microscopy confirmed that the intensity of the doxorubicin-derived fluorescence increased in the area where the microstructure was present, confirming that doxorubicin was significantly incorporated into the microstructure.
[0173] Example 15 Adhesion of sheet-shaped nanostructure β-CD was purchased from Fujifilm Wako Pure Chemical Industries, Ltd. EO 75 PO 30 EO 75 (Subscripts indicate unit numbers) were purchased from Sigma Aldrich.
[0174] The sheet-shaped nanostructure was prepared as follows: 18 mg of β-CD was dissolved in 1 mL of deionized water (pH about 7) at 23±1°C. EO 75 PO 30 EO 75 4 mg of β-CD was added to 1 mL of the prepared aqueous solution. The mixed solution was stirred by vortex for 1 minute. The solution was then placed on a shaker and aged. After one week, the precipitate and the liquid layer separated, and the complex formation was almost complete. The sample was then mixed with β-CD / EO 75 PO 30 EO 75 and named it.
[0175] The sheet-shaped nanostructure created is β-CD / EO. 75 PO 30 EO 75 The aqueous dispersion of Skin_β-CD / EO was dropped onto three types of solid substrates (pigskin, hair, and contact lenses), and the water was wiped off with filter paper before SEM observation. 75 PO 30 EO 75 , hair_β-CD / EO 75 PO 30 EO 75 , lens_β-CD / EO 75 PO 30 EO 75 , and named it as PPR_EO created in Example 4. 147PO 56 EO 147 The solution was dropped onto a pig's eye, washed with saline solution (0.9 wt%), and then wiped off with filter paper before observing under an optical microscope. 147 PO 56 EO 147 Let us assume that.
[0176] Skin_β-CD / EO 75 PO 30 EO 75 , hair_β-CD / EO 75 PO 30 EO 75 , lens_β-CD / EO 75 PO 30 EO 75 The SEM images of eye_PPR_EO are shown in Figs. 23(A) and (B), 24(A) and (B), and 25(A) and (B). 147 PO 56 EO 147 The photographs taken with an optical microscope are shown in Figure 26. In both cases, the adhesion of the sheet-shaped nanostructures was confirmed.
[0177] Example 16 UV-cutting function of sheet-shaped nanostructure β-CD was purchased from Fujifilm Wako Pure Chemical Industries, Ltd. EO 75 PO 30 EO 75 (Subscripts indicate unit numbers) were purchased from Sigma Aldrich.
[0178] The sheet-shaped nanostructure was prepared by the same method as in Example 15. The sample was β-CD / EO 75 PO 30 EO 75 and named it.
[0179] β-CD / EO 75 PO 30 EO 75 The UV-cutting ability of the dispersion water was evaluated using a UV-visible spectrophotometer (UV3150, Shimadzu Corporation). The wavelength of incident light was set to 250 nm to 800 nm, and the absorbance was measured.
[0180] The measurement results are shown in Figure 27. It was found that the transmittance was low in the UVA (315 to 400 nm) and UVB (290 to 320 nm) wavelength regions, and that light was transmitted in the visible wavelength region (400 nm to 700 nm).
[0181] Example 17 Gas barrier function of coating made of sheet-shaped nanostructure β-CD was purchased from Fujifilm Wako Pure Chemical Industries, Ltd. EO 75 PO 30 EO 75 (Subscripts indicate unit numbers) were purchased from Sigma Aldrich.
[0182] The sheet-shaped nanostructure was prepared by the same method as in Example 15. The sample was β-CD / EO 75 PO 30 EO 75 and named it.
[0183] β-CD / EO 75 PO 30 EO 75 5mL and 20mL of the dispersion water were passed through a porous membrane (PMMA-milipore: TYPE JCWP 10.0μm, hydrophilic, pore diameter approximately 10μm) to obtain β-CD / EO 75 PO 30 EO 75 These samples were then dried naturally at room temperature. 75 PO 30 EO 75 (5mL) and pоre-β-CD / EO 75 PO 30 EO 75 (20mL).
[0184] Porous membrane, pore-β-CD / EO 75 PO 30 EO 75 (5mL) and pоre-β-CD / EO 75 PO 30 EO 75 The SEM images of the porous membrane (20 mL) are shown in Figures 28(A), 28(B), and 28(C), respectively.75 PO 30 EO 75 (5mL) β-CD / EO 75 PO 30 EO 75 It was confirmed that the pores were not penetrated and remained in the membrane. 75 PO 30 EO 75 In the case of (20 mL), it was possible to confirm that the pores were completely covered.
[0185] pore-β-CD / EO 75 PO 30 EO 75 Since it was confirmed that the pores were completely covered in the sample (20 mL), we next used this to create a sample for evaluating oxygen permeability. The method for creating the sample is as follows: Nitrile rubber was dissolved in an organic solvent at a concentration of 2 wt%, and pore-β-CD / EO was added to the solution. 75 PO 30 EO 75 (20 mL). The sample was then taken out and air-dried at room temperature to obtain the pоre-β-CD / EO 75 PO 30 EO 75 A nitrile rubber film carrying 20 mL of ethylenediaminetetraacetate (EDTA) was prepared.
[0186] pore-β-CD / EO 75 PO 30 EO 75 The oxygen permeability of the nitrile rubber film carrying 20 mL of water was measured, and the oxygen permeability coefficient was 18.6 cc mm / (m 2 ·day·atm. The oxygen permeability coefficient was 18.6 cc·mm / (m 2 β-CD / EO 75 PO 30 EO 75 It was found that the material has oxygen barrier properties. The oxygen coefficient was measured using the following equipment and conditions: Measurement equipment: MOCON (registered trademark) coulometric oxygen permeability measurement equipment (OX-TRAN (registered trademark) 2 / 22L) Detector: Self-humidified coulometric sensor Compatible standards: JIS K7126-2 (Plastics - Films and sheets - Gas permeability test method - Part 2: Constant pressure method) (ISO 15105-2), ASTM D3985・F1927・F1307 Measurement temperature: 23℃ Relative humidity: 0% Effective membrane area: 1cm ^2
[0187] Example 18 Incorporation of drugs into sheet-shaped nanostructures Manufacturing Example 1 Encapsulation of anti-inflammatory drug (betamethasone) into microstructure 1 Betamethasone-encapsulated microstructures were prepared as follows. 30 mg of PPO4k (weight average molecular weight 4k: obtained from Sigma Aldrich) and 10 mg of betamethasone (obtained from Fujifilm Wako Pure Chemical Industries, Ltd.) were dissolved in 1 mL of deionized water (pH about 7) at 23 ± 1 °C. Next, 120 mg of γCD (obtained from CycloChem Co. Ltd.) was added to 1 mL of an aqueous solution of PPO4k and betamethasone. The mixed solution was stirred with a vortex for 1 minute. The solution was then placed on a shaker at room temperature and aged by shaking. After 30 minutes of shaking, the solution became slightly cloudy, and became even more cloudy after 2 hours. Shaking was continued at room temperature for 5 days.
[0188] Next, 800μL of the resulting cloudy liquid was placed in a 1.5mL centrifuge tube and centrifuged at 12000rpm for 5 minutes in a centrifuge (Kenis), resulting in the precipitation of a white solid paste at the bottom of the centrifuge tube. 600μL of the clear supernatant was removed from the centrifuge tube, and 800μL of a new γCD aqueous solution (γCD concentration 30mg / mL) was added to the remaining white solid paste to suspend the white solid, and centrifugation was performed again to remove 800μL of the supernatant. This series of steps of adding the γCD aqueous solution, centrifuging, and removing the supernatant was used as the chemical washing process, and the chemical washing process was repeated five times.
[0189] The white solid paste after washing with the chemicals was freeze-dried to obtain 95 mg of a white solid. The resulting white solid was designated as Microstructure-1.
[0190] The amount of betamethasone encapsulated in the microstructure-1 was calculated by measuring absorbance. 25 mg of the microstructure-1 was precisely weighed and dissolved in 1 mL of DMSO, and the absorbance of the obtained DMSO solution was measured by a spectrophotometer (using a quartz cell with an optical path length of 1 mm) to calculate the betamethasone concentration. The calculation was performed by creating a concentration-absorbance calibration curve at a predetermined wavelength (λ=260 nm) of the DMSO solution of betamethasone in advance, and the betamethasone concentration was calculated from the measured absorbance value and the calibration curve. The betamethasone concentration was calculated to be 1.0 mg / mL, and 1.0 mg of betamethasone was encapsulated in 25 mg of the microstructure-1, and the betamethasone encapsulation rate was 4.0 mass%.
[0191] Manufacturing Example 2: Encapsulation of betamethasone into microstructure 2 Betamethasone was encapsulated in the microstructure in the same manner as in Production Example 1, except that PEO4k (weight average molecular weight 4k: obtained from Sigma Aldrich) was used instead of PPO4k as the axial molecule. Drug washing was performed five times, and the white solid paste was freeze-dried to obtain 88 mg of a white solid. The obtained white solid is referred to as microstructure-2. The betamethasone encapsulation rate of the microstructure-2 was 8.8% by mass.
[0192] Manufacturing Example 3: Encapsulating a diuretic (spironolactone) into a microstructure 1 Spironolactone was encapsulated in the microstructure in the same manner as in Production Example 1, except that spironolactone (obtained from Tokyo Chemical Industry Co., Ltd.) was used instead of betamethasone as the drug. Drug washing was performed five times, and the white solid paste was freeze-dried to obtain 90 mg of a white solid. The resulting white solid is referred to as microstructure-3. The spironolactone encapsulation rate of microstructure-3 was 7.4% by mass.
[0193] Production Example 4: Encapsulation of spironolactone in microstructure 2 Spironolactone was encapsulated in the microstructure in the same manner as in Production Example 3, except that PEO4k was used instead of PPO4k as the axial molecule. Chemical washing was performed five times, and the white solid paste was freeze-dried to obtain 80 mg of a white solid. The resulting white solid is referred to as microstructure-4. The spironolactone encapsulation rate of microstructure-4 was 10.1% by mass.
[0194] Manufacturing Example 5 Encapsulation of anti-inflammatory drug (hydrocortisone) into microstructure 1 Spironolactone was encapsulated in the microstructure in the same manner as in Production Example 1, except that hydrocortisone (obtained from Tokyo Chemical Industry Co., Ltd.) was used instead of betamethasone as the drug. Drug washing was performed five times, and the white solid paste was freeze-dried to obtain 78 mg of a white solid. The resulting white solid is referred to as microstructure-5. The spironolactone encapsulation rate of microstructure-5 was 3.6% by mass.
[0195] Production Example 6 Encapsulation of hydrocortisone into microstructure 2 Hydrocortisone was encapsulated in the microstructure in the same manner as in Production Example 5, except that PEO4k was used instead of PPO4k as the axial molecule. Drug washing was performed five times, and the white solid paste was freeze-dried to obtain 83 mg of a white solid. The resulting white solid is referred to as Microstructure-6. The hydrocortisone encapsulation rate in Microstructure-6 was 5.8% by mass.
[0196] Production Example 7 Encapsulation of anti-inflammatory drug (dexamethasone) into microstructure 1 Dexamethasone was encapsulated in the microstructure in the same manner as in Production Example 1, except that dexamethasone (obtained from Tokyo Chemical Industry Co., Ltd.) was used instead of betamethasone as the drug, and the drug concentration-absorbance calibration curve was created using absorbance values at a wavelength λ=270 nm. Drug washing was performed five times, and the white solid paste was freeze-dried to obtain a white solid. The resulting white solid is referred to as microstructure-7. The dexamethasone encapsulation rate in microstructure-7 was 2.3% by mass.
[0197] Production Example 8 Encapsulation of dexamethasone into microstructure 2 Except for using PEO4k instead of PPO4k as the axial molecule, the same process as in Production Example 7 was used to encapsulate dexamethasone in the microstructure. Drug washing was performed five times, and the white solid paste was freeze-dried to obtain 68 mg of a white solid. The resulting white solid is referred to as microstructure-8. The dexamethasone encapsulation rate of microstructure-8 was 8.3% by mass.
[0198] Manufacturing Example 9 Encapsulation of anticancer drug (doxorubicin hydrochloride) into microstructure 1 Doxorubicin hydrochloride was encapsulated in the microstructure in the same manner as in Production Example 1, except that doxorubicin hydrochloride (obtained from Tokyo Chemical Industry Co., Ltd.) was used instead of betamethasone as the drug, and the drug concentration-absorbance calibration curve was created using absorbance values at a wavelength λ=500 nm. Drug washing was performed four times, and the white solid paste was freeze-dried to obtain 80 mg of a white solid. The resulting white solid is referred to as microstructure-9. The doxorubicin hydrochloride encapsulation rate in microstructure-9 was 0.2% by mass.
[0199] Manufacturing Example 10: Encapsulation of anticancer drug (doxorubicin hydrochloride) into microstructure 2 Doxorubicin hydrochloride was encapsulated in the microstructure in the same manner as in Production Example 9, except that PPO2k (weight average molecular weight 2k: obtained from Sigma Aldrich) was used instead of PPO4k as the axial molecule. Drug washing was performed four times, and the white solid paste was freeze-dried to obtain 75 mg of a white solid. The resulting white solid is referred to as microstructure-10. The doxorubicin hydrochloride encapsulation rate of the microstructure-10 was 0.2% by mass.
[0200] Production Example 11 Encapsulation of anticancer drug (doxorubicin hydrochloride) into microstructure 3 Doxorubicin hydrochloride was encapsulated in the microstructure in the same manner as in Production Example 9, except that PPO0.7k (weight average molecular weight 0.7k: obtained from Fujifilm Wako Pure Chemical Industries, Ltd.) was used instead of PPO4k as the axial molecule. Drug washing was performed five times, and the white solid paste was freeze-dried to obtain 50 mg of a white solid. The obtained white solid is referred to as microstructure-11. The doxorubicin hydrochloride encapsulation rate of microstructure-11 was 0.2% by mass.
[0201] Manufacturing Example 12 Encapsulation of anticancer drug (doxorubicin hydrochloride) into microstructure 4 Doxorubicin hydrochloride was encapsulated in the microstructure in the same manner as in Production Example 9, except that PEO4k was used instead of PPO4k as the axial molecule. Drug washing was performed five times, and the white solid paste was freeze-dried to obtain 81 mg of a white solid. The resulting white solid is referred to as microstructure-12. The doxorubicin hydrochloride encapsulation rate of the microstructure-12 was 0.3% by mass.
[0202] Production Example 13: Encapsulation of glaucoma treatment drug (dorzolamide hydrochloride) in microstructure Dorzolamide hydrochloride was encapsulated in the microstructure in the same manner as in Production Example 12, except that dorzolamide hydrochloride (obtained from Tokyo Chemical Industry Co., Ltd.) was used instead of doxorubicin hydrochloride as the drug, and the drug concentration-absorbance calibration curve was created using absorbance values at a wavelength λ=260 nm. Drug washing was performed five times, and the white solid paste was freeze-dried to obtain 88 mg of a white solid. The resulting white solid is referred to as microstructure-13. The dorzolamide hydrochloride encapsulation rate in microstructure-13 was 1.3% by mass.
[0203] Production Example 14: Encapsulating a dementia treatment drug (donepezil hydrochloride) in a microstructure Encapsulation of donepezil hydrochloride into the microstructure was carried out in the same manner as in Production Example 12, except that the drug was changed from doxorubicin hydrochloride to donepezil hydrochloride (obtained from Tokyo Chemical Industry Co., Ltd.) and the drug concentration-absorbance calibration curve was created at the absorbance value at a wavelength λ=270 nm. Drug washing was carried out four times, and the white solid paste was freeze-dried to obtain 70 mg of a white solid. The obtained white solid is referred to as microstructure-14. The encapsulation rate of donepezil hydrochloride in microstructure-14 was 1.5% by mass.
[0204] Production Example 15 Encapsulation of donepezil hydrochloride in a microstructure 2 Encapsulation of donepezil hydrochloride into the microstructure was carried out in the same manner as in Production Example 14, except that the axial molecule was changed from PPO4k to PEO4k. Drug washing was carried out five times, and the white solid paste was freeze-dried to obtain 91 mg of a white solid. The obtained white solid is referred to as microstructure-15. The encapsulation rate of donepezil hydrochloride in microstructure-15 was 1.0 mass%.
[0205] Production Example 16: Encapsulating an anticancer drug (nimustine hydrochloride) in a microstructure Dorzolamide hydrochloride was encapsulated in the microstructure in the same manner as in Production Example 12, except that the drug was changed from doxorubicin hydrochloride to nimustine hydrochloride (obtained from Tokyo Chemical Industry Co., Ltd.) and the drug concentration-absorbance calibration curve was created using absorbance values at a wavelength λ=270 nm. Drug washing was performed five times, and the white solid paste was freeze-dried to obtain 58 mg of a white solid. The resulting white solid is referred to as microstructure-16. The dorzolamide hydrochloride encapsulation rate in microstructure-13 was 0.2% by mass.
[0206] Manufacturing Example 17: Encapsulating an anticancer drug (dacarbazine) into a microstructure Dacarbazine was encapsulated in the microstructure in the same manner as in Production Example 12, except that the drug was changed from doxorubicin hydrochloride to dacarbazine (obtained from Tokyo Chemical Industry Co., Ltd.) and the drug concentration-absorbance calibration curve was created using absorbance values at a wavelength λ=350 nm. Drug washing was performed five times, and the white solid paste was freeze-dried to obtain 69 mg of a white solid. The resulting white solid is referred to as microstructure-17. The dacarbazine encapsulation rate of microstructure-13 was 0.5% by mass.
[0207] Example 18: Encapsulating anticancer drug (cytarabine) in microstructures Cytarabine was encapsulated in the microstructure in the same manner as in Production Example 12, except that the drug was changed from doxorubicin hydrochloride to cytarabine (obtained from Tokyo Chemical Industry Co., Ltd.) and the drug concentration-absorbance calibration curve was created using absorbance values at a wavelength λ=280 nm. Drug washing was performed five times, and the white solid paste was freeze-dried to obtain 93 mg of a white solid. The resulting white solid is referred to as microstructure-18. The cytarabine encapsulation rate of microstructure-18 was 0.1% by mass.
[0208] Production Example 19 Encapsulation of clofibrate in microstructure 1 Clofibrate (obtained from Tokyo Chemical Industry Co., Ltd.) was used as the drug instead of betamethasone, and a γCD solution (γCD concentration 30 mg / mL) in a mixed solvent (water / ethanol = 50 vol% / 50 vol%) was used as the cleaning solution in the drug washing process. The drug concentration-absorbance calibration curve was created using the absorbance value at a wavelength λ = 280 nm. Except for this, clofibrate was encapsulated in the microstructure in the same manner as in Production Example 1. Drug washing was performed five times, and the white solid paste was freeze-dried to obtain a white solid. The obtained white solid is referred to as microstructure-19. The clofibrate encapsulation rate of microstructure-19 was 6.7% by mass.
[0209] Production Example 20 Encapsulation of clofibrate in microstructure 2 Clofibrate was encapsulated in the microstructure in the same manner as in Production Example 15, except that PEO4k was used instead of PPO4k as the axial molecule. After washing five times, the white solid paste was freeze-dried to obtain a white solid. The resulting white solid is referred to as Microstructure-20. The encapsulation rate of clofibrate in Microstructure-20 was 2.9%.
[0210] Manufacturing Example 21 Encapsulating an anticancer drug (5-fluorouracil) into a microstructure 1 5-fluorouracil was encapsulated in the microstructure in the same manner as in Production Example 15, except that 5-fluorouracil (obtained from Tokyo Chemical Industry Co., Ltd.) was used instead of betamethasone as the drug, and the drug concentration-absorbance calibration curve was created using absorbance values at a wavelength λ=270 nm. Washing was performed five times, and the white solid paste was freeze-dried to obtain a white solid. The obtained white solid is referred to as microstructure-21. The encapsulation rate of 5-fluorouracil in microstructure-21 was 0.4% by mass.
[0211] Production Example 22 Encapsulation of 5-fluorouracil into microstructure 2 Except for using PEO4k instead of PPO4k as the axial molecule, 5-fluorouracil was encapsulated in the microstructure in the same manner as in Production Example 17. The white solid paste was washed four times and freeze-dried to obtain a white solid. The resulting white solid is called microstructure-22. The encapsulation rate of 5-fluorouracil in microstructure-22 was 0.1% by mass.
[0212] Manufacturing Example 23 Encapsulating an anticancer drug (docetaxel) into a microstructure 1 Docetaxel was encapsulated in the microstructure in the same manner as in Production Example 15, except that docetaxel (obtained from Tokyo Chemical Industry Co., Ltd.) was used instead of betamethasone as the drug, and the drug concentration-absorbance calibration curve was created using absorbance values at a wavelength λ of 285 nm. Washing was performed five times, and the white solid paste was freeze-dried to obtain a white solid. The obtained white solid is referred to as microstructure-23. The docetaxel encapsulation rate of microstructure-23 was 0.5% by mass.
[0213] Production Example 24 Encapsulation of docetaxel in microstructure 2 Docetaxel was encapsulated in the microstructure in the same manner as in Production Example 19, except that PEO4k was used instead of PPO4k as the axial molecule. Washing was performed five times, and the white solid paste was freeze-dried to obtain a white solid. The resulting white solid is referred to as microstructure-24. The docetaxel encapsulation rate of microstructure-24 was 2.9% by mass.
[0214] [Table 1]
[0215] Example 19 Incorporation of fluorescent molecules into sheet-shaped nanostructures Manufacturing Example 25: Encapsulating fluorescent molecules (fluorescein isothiocyanate (FITC)) in microstructures The fluorescent molecule FITC was used instead of the drug betamethasone, and the fluorescent molecule concentration-absorbance calibration curve was created using absorbance values at a wavelength λ of 280 nm, but the same process was used to enclose FITC in the microstructure as in Production Example 1. The fluorescent molecule was washed six times, and the pale yellow solid paste was freeze-dried to obtain 70 mg of a pale yellow solid. The resulting pale yellow solid is referred to as microstructure-25. The FITC entrapment rate in microstructure-25 was 0.2% by mass. In addition, 10 mg of microstructure-25 was added to 200 μL of γCD aqueous solution (γCD concentration: 30 mg / mL) and ultrasonicated for 1 minute with an ultrasonic cleaner to disperse the microstructure. The obtained microstructure dispersion was observed with a fluorescence microscope (Nikon DS-Fi3, manufactured by Nikon Corporation). Light with a wavelength of 470 nm was used as the excitation light for the fluorescence observation, and fluorescence emission was observed inside the microstructure, confirming the inclusion of FITC inside the microstructure.
[0216] Production Example 26: Inclusion of Rhodamine B in a microstructure Rhodamine B was encapsulated in the microstructure in the same manner as in Production Example 25, except that rhodamine B was used instead of FITC as the fluorescent molecule, and PEO20k was used instead of PPO4k as the axial molecule. Six washings were performed, and the reddish purple solid paste was freeze-dried to obtain 66 mg of a pink solid. The obtained reddish purple solid is referred to as microstructure-26. The encapsulation rate of rhodamine B in microstructure-26 was 0.1% by mass. Furthermore, in the same manner as in Example 25, observation with a fluorescent microscope was performed, and fluorescence emission was observed inside the microstructure, confirming the inclusion of rhodamine B inside the microstructure.
[0217] Example 27: Inclusion of uranine in a microstructure Uranine was encapsulated in the microstructure in the same manner as in Production Example 25, except that uranine was used instead of FITC as the fluorescent molecule, and PPO2k was used instead of PPO4k as the axial molecule. Six washings were performed, and the reddish purple solid paste was freeze-dried to obtain 75 mg of a pink solid. The resulting pink solid is referred to as microstructure-27. The uranine encapsulation rate of microstructure-27 was 0.1% by mass. Furthermore, in the same manner as in Example 25, observation was performed using a fluorescent microscope to observe fluorescence emission inside the microstructure, thereby confirming the inclusion of uranine inside the microstructure.
[0218] [Table 2] [Explanation of symbols]
[0219] 1...structure, 2...pseudopolyrotaxane and / or polyrotaxane, 4...space between multiple pseudopolyrotaxanes and / or polyrotaxanes, 6...space partitioned by multiple cyclic molecules, 10...chain polymer, 20...cyclic molecule, 24...opening partitioned by one cyclic molecule, 30...substance.
Claims
1. A structure having a plurality of pseudopolyrotaxanes and / or polyrotaxanes each having a chain polymer skewered and included in an opening of a cyclic molecule, Both ends of the chain polymer are accommodated in a column of multiple cyclic molecules; At least a portion of the multiple pseudopolyrotaxanes and / or polyrotaxanes are arranged in series with each other and interact with each other; and A structure in which at least a portion of a plurality of pseudopolyrotaxanes and / or polyrotaxanes are arranged in parallel with each other.
2. The structure of claim 1 , wherein the chain polymer is a single chain.
3. 3. The structure according to claim 1, wherein the linear polymer is included in the openings of three or more cyclic molecules in a skewered manner per one linear polymer.
4. The structure according to any one of claims 1 to 3, further comprising a substance bound to a chain polymer, bound to a cyclic molecule, or held inside a space between a plurality of pseudopolyrotaxanes and / or polyrotaxanes, an opening formed by one cyclic molecule, or a space formed by a plurality of cyclic molecules.
5. 5. The structure according to claim 4, wherein the substance is at least one selected from the group consisting of a drug, a fluorescent substance, and a chromogenic enzyme.
6. 6. The structure according to claim 1, wherein the length of the chain polymer is from 1 nm to 2000 nm.
7. The structure according to any one of claims 1 to 6, wherein the chain polymer comprises a portion made of polyethylene glycol (PEG) or polypropylene glycol (PPG).
8. 8. The structure according to claim 1, wherein the cyclic molecule is at least one selected from the group consisting of cyclodextrin, crown ether, pillararene, calixarene, cyclophane, and derivatives thereof.
9. The structure according to any one of claims 1 to 8, wherein the one or more through holes are provided which penetrate the structure and occupy a space larger than the volume occupied by one pseudopolyrotaxane and / or polyrotaxane.
10. A structure comprising a plurality of pseudopolyrotaxanes and / or polyrotaxanes each having a chain polymer skewered and included in an opening of a cyclic molecule, At least a portion of the multiple pseudopolyrotaxanes and / or polyrotaxanes are arranged in series with each other, At least a portion of the multiple pseudopolyrotaxanes and / or polyrotaxanes are arranged in parallel with each other, and A structure in which one or more through holes are provided, the through holes penetrating the structure and occupying a space larger than the volume occupied by one pseudopolyrotaxane and / or polyrotaxane.
11. The structure according to any one of claims 1 to 10, wherein the structure is any one of the following (a) to (c). (a) A rod-shaped structure in which the linear polymer has a weight average molecular weight of 200 to 10,000. (b) A cube-shaped structure in which the linear polymer has a weight average molecular weight of 1,000 to 20,000. (c) A sheet-shaped structure in which the linear polymer 10 has a weight average molecular weight of 2,000 to 200,000.
12. A method for producing a structure having a plurality of pseudopolyrotaxanes and / or polyrotaxanes each having a chain polymer skewered and included in an opening of a cyclic molecule, comprising the steps of: A method comprising the step of: allowing a plurality of pseudo-polyrotaxanes and / or polyrotaxanes contained in a column in which both ends of a chain polymer are made of a plurality of cyclic molecules to interact with each other, thereby arranging at least a portion of the plurality of pseudo-polyrotaxanes and / or polyrotaxanes in series with each other and in parallel with each other.
Citation Information
Patent Citations
Polyrotaxane fiber
JP2010261134A
Manufacturing method of alkylated polyrotaxane
JP2018016671A
Separable nanosheet and production method therefor
WO2020013215A1